Method for producing polyester film using recovered polyester resin, and polyester film
By mixing the recovered polyester resin with the polyester resin containing aluminum compound and phosphorus compound, the problem of deterioration in the reuse process of recycled polyester resin is solved, and efficient recycling and low environmental load polyester film preparation is achieved.
Patent Information
- Application Number
- CN202380058361.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-17
- Filing Date
- 2023-08-16
- Publication Date
- 2025-03-18
AI Technical Summary
The existing polyester resins are prone to deterioration during recycling and reuse, resulting in a decrease in coloring and molecular weight, affecting the performance and recycling efficiency of the film.
By mixing the recovered polyester resin with a polyester resin containing an aluminum compound and a phosphorus compound, a polyester film with high recycling efficiency and less deterioration was prepared.
In the case of recovering polyester resin as a raw material, it is achieved to reduce the deterioration of the resin and the decrease in molecular weight, and to improve the recycling efficiency of the polyester film and the environmental low load effect.
Smart Images

Figure BDA0005263576180000211 
Figure BDA0005263576180000221 
Figure BDA0005263576180000231
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a polyester film containing recycled polyester resin and the polyester film. Background Art
[0002] Polyester resins represented by polyethylene terephthalate (PET) and polyethylene naphthalate (PEN) have excellent transparency, mechanical properties and chemical properties. Depending on the properties of each polyester resin, they are widely used in various fields, such as fibers for clothing or industrial materials, various films or sheets for packaging or industrial use, bottles (such as hollow molded bodies), etc.
[0003] For example, in recent years, hollow molded bodies made of polyester resins have become indispensable items in life. On the other hand, with the increase in the use of hollow molded bodies, various problems such as resource depletion, increase in marine garbage, and global warming have arisen. As one of the methods to solve such problems, recycling and reusing used hollow molded bodies such as polyester bottles, i.e., a so-called recycling / regeneration recycling system, has attracted attention. In the polyester film, various proposals have been made to produce films using such recycled polyester resins as a raw material.
[0004] However, in the case of polyester resins using widely used antimony compounds, titanium compounds or germanium compounds as polymerization catalysts, when the used polyester resins are recovered and regenerated, the polyester resins are deteriorated and coloring and molecular weight reduction occur, and improvements are required. In particular, when forming films, the ear-shaped parts and other stretching wastes generated during film production are often reused as raw material resins, and therefore a resin is required that has less coloring and molecular weight reduction caused by heating and melting even as recycled polyester resins.
[0005] As a method for solving the above-mentioned problems, there is known a method of adding a hindered phenol compound during the production of a polyester resin using an antimony compound, a titanium compound or a germanium compound as a polymerization catalyst (for example, refer to Patent Documents 1 and 2).
[0006] In the methods described in Patent Documents 1 and 2, the thermal oxidation stability is improved, but further improvement is required from the viewpoint of suppressing the deterioration of physical properties during recycling. [Prior art literature] [Patent Literature]
[0007] [Patent Document 1] International Publication No. 2013 / 154042 [Patent Document 2] International Publication No. 2013 / 154043 [Patent Document 3] International Publication No. 2007 / 032325 [Patent Document 4] Japanese Patent Application Publication No. 2006-169432 Summary of the invention [Problems to be solved by the invention]
[0008] On the other hand, the applicant has discovered a catalyst having excellent thermal stability for polyester. Specifically, the applicant has discovered that when a catalyst composed of an aluminum compound described in Patent Documents 3 and 4 and a phosphorus compound having a hindered phenol structure is used for polyester, transparency and thermal stability are improved. However, there has been no research on recycling a used polyester resin, particularly a used polyester resin using at least one selected from an antimony compound, a titanium compound, and a germanium compound as a polymerization catalyst, and preparing a film.
[0009] The present invention is an invention for overcoming the above-mentioned problems of the prior art, and its purpose is to provide a method for producing a polyester film, which can suppress coloration and molecular weight reduction when using a used polyester resin selected from at least one of antimony compounds, titanium compounds and germanium compounds as a polymerization catalyst to produce a polyester film, and even when the film waste is reused, the deterioration is less, thereby improving the recycling efficiency, and to provide a polyester film containing the recycled polyester resin.
Methods to solve the problem
[0010] The present inventors conducted intensive research to solve the above-mentioned problems and found that by adding a polyester resin containing an aluminum compound and a phosphorus compound to a recycled polyester resin containing at least one element selected from antimony, titanium and germanium, a polyester film with excellent recycling efficiency and less coloration or molecular weight loss can be produced.
[0011] That is, the present invention is constituted as follows. [Item 1] A method for producing a polyester film, characterized in that it includes: a step of mixing a recovered polyester resin (A) with a polyester resin (B) containing an aluminum compound and a phosphorus compound, wherein the polyester resin (A) satisfies the following (1) to (3), and the polyester resin (B) satisfies the following (4). (1) The polyester resin (A) contains at least one element selected from antimony, titanium and germanium. (2) The total content of antimony, titanium and germanium in the polyester resin (A) is 2 to 500 ppm by mass (3) The intrinsic viscosity of the polyester resin (A) is 0.5 to 0.8 dl / g (4) The polyester resin (B) is a resin obtained by polycondensing a raw material containing di-2-hydroxyethyl terephthalate obtained by decomposing a polyester resin. [Item 2] The method for producing a polyester film according to item 1, wherein the polyester resin (B) satisfies the following (5) and (6). (5) The content of aluminum in the polyester resin (B) is 5 to 50 ppm by mass (6) The phosphorus content in the polyester resin (B) is 5 to 1000 ppm by mass [Item 3] The method for producing a polyester film according to item 1 or 2, wherein the mixing step comprises: melt-mixing the polyester resin (A) and the polyester resin (B) to prepare a polyester resin composition (C). [Item 4] The method for producing a polyester film according to any one of items 1 to 3, wherein the mixing step includes further mixing a polyester resin (D) different from the polyester resin (A) and the polyester resin (B). [Item 5] A method for producing a polyester film, characterized in that it includes: a step of mixing a polyester resin composition (C) which is a molten mixture of a recovered polyester resin (A) and a polyester resin (B) containing an aluminum compound and a phosphorus compound, with a polyester resin (D) different from the polyester resin (A) and the polyester resin (B), wherein the polyester resin (A) satisfies the following (1) to (3), and the polyester resin (B) satisfies the following (4). (1) The polyester resin (A) contains at least one element selected from antimony, titanium and germanium. (2) The total content of antimony, titanium and germanium in the polyester resin (A) is 2 to 500 ppm by mass (3) The intrinsic viscosity of the polyester resin (A) is 0.5 to 0.8 dl / g (4) The polyester resin (B) is a resin obtained by polycondensing a raw material containing di-2-hydroxyethyl terephthalate obtained by decomposing a polyester resin. [Item 6] The method for producing a polyester film according to any one of Items 3 to 5, wherein the polyester resin composition (C) has an intrinsic viscosity retention rate of 89% or more as obtained by the following formula. Intrinsic viscosity retention rate (%) = Intrinsic viscosity of the sample after 1 re-melting / Intrinsic viscosity of the sample × 100 (The first remilled sample is a sample that has passed through a twin-screw extruder under the conditions of a temperature of 260°C, a screw speed of 200 rpm, and an output of 1.7 to 2.0 kg / h. The intrinsic viscosity is calculated by feeding a solution of 0.2 g of the sample and 20 ml of a mixed solvent of 1,1,2,2-tetrachloroethane and p-chlorophenol (mass ratio 1:3) to an Ubbelohde viscometer at 30°C.) [Item 7] The method for producing a polyester film according to any one of Items 1 to 6, wherein the polyester resin (A) has an intrinsic viscosity retention rate of 92% or less as obtained by the following formula. Intrinsic viscosity retention rate (%) = Intrinsic viscosity of the sample after 1 re-melting / Intrinsic viscosity of the sample × 100 (The first remilled sample is a sample that has passed through a twin-screw extruder under the conditions of a temperature of 260°C, a screw speed of 200 rpm, and an output of 1.7 to 2.0 kg / h. The intrinsic viscosity is calculated by feeding a solution of 0.2 g of the sample and 20 ml of a mixed solvent of 1,1,2,2-tetrachloroethane and p-chlorophenol (mass ratio 1:3) to an Ubbelohde viscometer at 30°C.) [Item 8] The method for producing a polyester film according to any one of items 1 to 7, wherein the polyester resin (B) has an intrinsic viscosity retention rate of 93% or more as obtained by the following formula. Intrinsic viscosity retention rate (%) = Intrinsic viscosity of the sample after 1 re-melting / Intrinsic viscosity of the sample × 100 (The first remilled sample is a sample that has passed through a twin-screw extruder under the conditions of a temperature of 260°C, a screw speed of 200 rpm, and an output of 1.7 to 2.0 kg / h. The intrinsic viscosity is calculated by feeding a solution of 0.2 g of the sample and 20 ml of a mixed solvent of 1,1,2,2-tetrachloroethane and p-chlorophenol (mass ratio 1:3) to an Ubbelohde viscometer at 30°C.) [Item 9] The method for producing a polyester film according to any one of items 4 to 8, wherein the polyester resin composition (E) containing the polyester resin (A), the polyester resin (B) and the polyester resin (D) has an intrinsic viscosity retention rate of 89% or more as obtained by the following formula. Intrinsic viscosity retention rate (%) = Intrinsic viscosity of the sample after 1 re-melting / Intrinsic viscosity of the sample × 100 (The first remilled sample is a sample that has passed through a twin-screw extruder under the conditions of a temperature of 260°C, a screw speed of 200 rpm, and an output of 1.7 to 2.0 kg / h. The intrinsic viscosity is calculated by feeding a solution of 0.2 g of the sample and 20 ml of a mixed solvent of 1,1,2,2-tetrachloroethane and p-chlorophenol (mass ratio 1:3) to an Ubbelohde viscometer at 30°C.) [Item 10] The method for producing a polyester film according to any one of items 1 to 9, wherein the content of the polyester resin (A) is 5 to 95 parts by mass based on 100 parts by mass of the total of the polyester resin (A) and the polyester resin (B). [Item 11] The method for producing a polyester film according to any one of items 4 to 10, wherein the content of the polyester resin (D) is 5 to 95 parts by mass based on 100 parts by mass of the total of the polyester resin (A), the polyester resin (B) and the polyester resin (D). [Item 12] The method for producing a polyester film according to any one of items 1 to 11, wherein the polyester film is a multilayer polyester film composed of at least two layers, and at least one surface layer is a layer not containing the polyester resin (A). [Item 13] The method for producing a polyester film according to any one of items 1 to 12, wherein the phosphorus compound has a phosphorus element and a phenol structure in the same molecule. [Item 14] The method for producing a polyester film according to any one of Items 1 to 13, wherein the polyester resin (A) contains at least an antimony element and a germanium element. [Item 15] The method for producing a polyester film according to any one of Items 1 to 14, wherein the polyester resin (A) contains at least an isophthalic acid structural unit as a copolymerization component. [Item 16] A polyester film, characterized in that the polyester film is composed of a polyester resin composition (E) of a recycled polyester resin (A) and a polyester resin (B) containing an aluminum compound and a phosphorus compound, wherein the polyester resin (A) satisfies the following (1) to (3), and the polyester resin (B) satisfies the following (4). (1) The polyester resin (A) contains at least one element selected from antimony, titanium and germanium. (2) The total content of antimony, titanium and germanium in the polyester resin (A) is 2 to 500 ppm by mass (3) The intrinsic viscosity of the polyester resin (A) is 0.5 to 0.8 dl / g (4) The polyester resin (B) is a resin obtained by polycondensing a raw material of di-2-hydroxyethyl terephthalate containing a polyester resin decomposition component. [Item 17] The polyester film according to Item 16, wherein the polyester resin (B) satisfies the following (5) and (6). (5) The content of aluminum in the polyester resin (B) is 5 to 50 ppm by mass (6) The phosphorus content in the polyester resin (B) is 5 to 1000 ppm by mass [Item 18] The polyester film according to Item 16 or 17, wherein the polyester resin composition (E) further contains a polyester resin (D) different from the polyester resin (A) and the polyester resin (B). [Item 19] The polyester film according to any one of Items 16 to 18, wherein the polyester resin composition (E) has an intrinsic viscosity retention rate of 89% or more as obtained by the following formula. Intrinsic viscosity retention rate (%) = Intrinsic viscosity of the sample after 1 re-melting / Intrinsic viscosity of the sample × 100 (The first remilled sample is a sample that has passed through a twin-screw extruder under the conditions of a temperature of 260°C, a screw speed of 200 rpm, and an output of 1.7 to 2.0 kg / h. The intrinsic viscosity is calculated by feeding a solution of 0.2 g of the sample and 20 ml of a mixed solvent of 1,1,2,2-tetrachloroethane and p-chlorophenol (mass ratio 1:3) to an Ubbelohde viscometer at 30°C.) [Item 20] The polyester film according to any one of Items 16 to 19, wherein the polyester resin composition (E) constituting the film contains at least antimony element, germanium element, phosphorus element, and aluminum element. [Item 21] The polyester film according to Item 20, wherein at least one polyester resin contained in the polyester resin composition (E) constituting the film contains an isophthalic acid structural unit as a copolymerization component. [Item 22] The polyester film according to any one of Items 16 to 21, wherein the content ratio of antimony element / aluminum element is 0.5 or more and 200 or less on a mass basis. [Item 23] The polyester film according to any one of Items 16 to 22, wherein the content ratio of antimony element / (aluminum element and phosphorus element) is 0.1 or more and 100 or less on a mass basis. [Effects of the invention]
[0012] According to the present invention, even when recycled polyester is used as a raw material, a polyester film can be produced with less resin degradation, less molecular weight reduction, less coloration, etc. Furthermore, the proportion of recycled materials in the entire polyester film can be increased, and the low load effect on the environment can be further improved. DETAILED DESCRIPTION
[0013] The method for producing a polyester film of the present invention is characterized by comprising the step of mixing a recovered polyester resin (A) with a polyester resin (B) containing an aluminum compound and a phosphorus compound, wherein the polyester resin (A) satisfies the following (1) to (3) a predetermined catalyst, a predetermined catalyst amount, and a predetermined intrinsic viscosity, and the polyester resin (B) is a resin obtained by polycondensing a raw material containing bis-2-hydroxyethyl terephthalate as a decomposition component of the polyester resin and satisfying the following (4). The polyester resin (A) includes a recycled polyester resin product which is a physically recycled polyester resin, and the polyester resin (B) includes a polycondensate of a decomposed component of a polyester resin which is a chemically recycled polyester resin. The polyester film obtained by the present invention has high recycling efficiency and less molecular weight reduction, coloration, etc.
[0014] [Polyester resin (A)] The polyester resin (A) is a resin obtained by recycling used polyester resin. The used polyester resin (A) refers to a resin that has been melted once in order to manufacture a polyester molded body. Examples thereof include recycled PET bottles, containers such as trays, fibers or products, outflow products before product sorting during manufacturing, Class B products that have not been shipped to the market, ear-shaped portions for holding during film stretching, cut tails, and molded products returned due to complaints, etc. The polyester resin (A) may be, for example, a single polyester resin product recyclate such as recycled PET bottles or ear-shaped parts of films, or a mixture of different polyester resin product recyclates. The shape of the polyester resin (A) is preferably a shape that can be easily mixed with the polyester resin (B). Examples of the shape of the polyester resin (A) include chips, flakes, and powders.
[0015] The polyester resin (A), like the polyester resin (B) described below, is preferably a polymer of a polyvalent carboxylic acid component and a polyol component. Examples of the polycarboxylic acid component and the polyol component include the same components as those for the polyester resin (B) described below. The polycarboxylic acid component is preferably a dicarboxylic acid (preferably an aromatic dicarboxylic acid) such as isophthalic acid and terephthalic acid, and the polyol component is preferably a diol (preferably ethylene glycol) such as ethylene glycol, diethylene glycol, neopentyl glycol, 1,6-hexanediol, and 1,4-cyclohexanediol. Among them, the polyester resin (A) preferably contains an ethylene terephthalate structural unit which is a polycondensate of terephthalic acid as a polycarboxylic acid component and ethylene glycol as a polyol component. The polyester resin (A) preferably contains 50 mol% or more of ethylene terephthalate structural units in 100 mol% of the longest structural unit constituting the polyester resin, more preferably 70 mol% or more, further preferably 80 mol% or more, and particularly preferably 90 mol% or more. As the polycarboxylic acid component other than terephthalic acid and the polyol component other than ethylene glycol, the components described in the polyester resin (B) below can be used.
[0016] From the viewpoint of quality management and improving recycling efficiency, the polyester resin (A) is preferably a polyethylene terephthalate resin. In this case, the polyester resin (A) may contain at least an isophthalic acid structural unit as a copolymerization component, and when all polycarboxylic acid component structural units are set to 100 mol%, the lower limit of the content of the isophthalic acid structural unit is preferably 0.02 mol%, more preferably 0.05 mol%, further preferably 0.1 mol%, particularly preferably 0.2 mol%, and most preferably 0.3 mol%. The upper limit is preferably 5.0 mol%, more preferably 4.0 mol%, further preferably 3.0 mol%, particularly preferably 2.5 mol%, and most preferably 2.0 mol%.
[0017] Diethylene glycol as a polyol component is not contained only in the polyester resin as a by-product of ethylene glycol during polyester polymerization, but may also be added during polymerization in order to adjust crystallization. When all polyol component structural units are set to 100 mol%, the lower limit of the content of the diethylene glycol structural unit in the polyester resin (A) is preferably 0.5 mol%, more preferably 0.8 mol%, further preferably 1.0 mol%, particularly preferably 1.2 mol%, and most preferably 1.4 mol%. The upper limit is preferably 5.0 mol%, more preferably 4.0 mol%, further preferably 3.5 mol%, and particularly preferably 3.0 mol%.
[0018] The copolymer components other than isophthalic acid and diethylene glycol of the polyester resin (A) (for example, phthalic acid, naphthalene dicarboxylic acid, neopentyl glycol, 1,6-hexanediol, 1,4-cyclohexanediol) may be respectively present in the polycarboxylic acid component and the polyol component. When all the polycarboxylic acid component structural units are set to 100 mol% and all the polyol component structural units are set to 100 mol%, the upper limit is preferably 3.0 mol%, more preferably 2.5 mol%, and even more preferably 2.0 mol%.
[0019] When the total amount of all polycarboxylic acid component structural units and all polyol component structural units is 200 mol%, the total amount of copolymer components (preferably copolymer components other than terephthalic acid and ethylene glycol) of the polyester resin (A) is preferably 0.5 mol%, more preferably 1.0 mol%, further preferably 1.5 mol%, and particularly preferably 2.0 mol% in terms of the total amount of copolymer components of the polycarboxylic acid component and the copolymer components of the polyol component. The upper limit is preferably 7.0 mol%, more preferably 6.0 mol%, further preferably 5.0 mol%, and particularly preferably 4.0 mol%. When the amount exceeds the above upper limit, the heat resistance and mechanical strength of the obtained polyester film may be reduced. In order to prevent this, the amount of the recycled polyester resin (A) added may be limited.
[0020] Polyester resin (A) (1) The polyester resin (A) contains at least one element selected from antimony, titanium and germanium. That is, the polyester resin (A) is produced by using at least one polymerization catalyst selected from antimony compounds, titanium compounds and germanium compounds in a catalytic amount. The polyester resin (A) preferably contains at least two elements selected from antimony, titanium and germanium, more preferably contains at least antimony and germanium, and further preferably contains antimony, titanium and germanium.
[0021] Polyester resin (A) (2) The total content of antimony, titanium and germanium in the polyester resin (A) is 2 to 500 mass ppm, preferably 5 to 400 mass ppm, more preferably 10 to 300 mass ppm, and further preferably 50 to 250 mass ppm. When it is greater than 500 mass ppm, the intrinsic viscosity retention rate of the polyester resin composition (C) described below may become insufficient. In addition, in this specification, mass ppm means 10 -4 quality%.
[0022] The content of antimony element in the polyester resin (A) is preferably 2 to 500 mass ppm, more preferably 5 to 400 mass ppm, further preferably 10 to 300 mass ppm, and further preferably 50 to 250 mass ppm. The content of the germanium element in the polyester resin (A) is preferably 0.1 to 50 mass ppm, more preferably 0.5 to 30 mass ppm, and even more preferably 1 to 10 mass ppm. The content of the titanium element in the polyester resin (A) is preferably 0.01 to 10 mass ppm, more preferably 0.02 to 5 mass ppm, and even more preferably 0.03 to 3 mass ppm. The polyester resin (A) may be one kind or a combination of two or more kinds. When two or more kinds of the polyester resins (A) are used, the contents of the above elements may be average values. The contents of antimony, titanium and germanium can be measured, for example, by the method described in the following Examples.
[0023] The polyester resin (A) may contain a colorant, lubricant particles, an ultraviolet absorber, a melt resistivity adjuster, an antistatic agent, an antioxidant, a heat stabilizer, and the like.
[0024] Polyester resin (A) (3) The intrinsic viscosity of the polyester resin (A) is preferably 0.5 to 0.8 dl / g, more preferably 0.55 to 0.77 dl / g, and even more preferably 0.57 to 0.75 dl / g. When the intrinsic viscosity of the polyester resin (A) is less than the above range, the mechanical strength and impact resistance of the polyester film produced using the polyester resin (A) may become insufficient. On the other hand, when the intrinsic viscosity of the polyester resin (A) is greater than the above range, the local shear heat generation increases when the polyester resin (A) and the polyester resin (B) are mixed (preferably mixed and melted), the resin may deteriorate, and the stress increases during stretching, which may make the production of the film difficult. In addition, the intrinsic viscosity and content of the mixed polyester resin (B) may be limited. The intrinsic viscosity of the polyester resin (A) can be measured as described in the examples.
[0025] Since the polyester resin used in the present invention is repeatedly recycled and melted at high temperature during recycling, the change rate of the intrinsic viscosity of the recycled polyester resin relative to the intrinsic viscosity of the polyester resin before recycling, that is, the intrinsic viscosity retention rate is used as an index. The intrinsic viscosity retention rate of the polyester resin (A) is preferably 92% or less, more preferably 91% or less, further preferably 90% or less, and particularly preferably 89% or less. When the intrinsic viscosity retention rate of the polyester resin (A) is higher than 92%, the effect of improving the recycling efficiency by adding the polyester resin (B) may become saturated. The method for measuring the intrinsic viscosity retention rate is as follows. The intrinsic viscosity retention rate of the polyester resin (A) is preferably 70% or more, more preferably 75% or more, and further preferably 80% or more. When the intrinsic viscosity retention rate of the polyester resin (A) is less than 70%, even if the polyester resin (B) is added, a sufficient improvement effect cannot be obtained, and the amount of the polyester resin (A) used needs to be suppressed to be low.
[0026] When the polyester resin (A) is a recycled PET bottle, the amount of CT (cyclic trimer) contained in the polyester resin (A) is preferably 9000 mass ppm or less, more preferably 8000 mass ppm or less, further preferably 7500 mass ppm or less, and particularly preferably 7000 mass ppm or less. The CT content is preferably 4000 mass ppm or more, more preferably 4500 mass ppm or more, and further preferably 4900 mass ppm or more.
[0027] The polyester resin (A) is preferably a polyester resin produced using only at least one polymerization catalyst selected from antimony compounds, titanium compounds and germanium compounds, but may contain a polyester resin produced using a polymerization catalyst composed of an aluminum compound and a phosphorus compound. The polyester resin produced using at least one polymerization catalyst selected from antimony compounds, titanium compounds and germanium compounds in the polyester resin (A) is preferably more than 50% by mass, more preferably 70% by mass or more, further preferably 80% by mass or more, further preferably 90% by mass or more, and particularly preferably 95% by mass or more.
[0028] The polyester resin (A) may be a resin obtained by melting and pelletizing a recovered molded product, but is preferably in a state of being directly pulverized without melting. From the perspective of handling, the pulverized product is preferably in a shape in which the longest distance between any two points is preferably 3 to 30 mm, more preferably 5 to 20 mm. In addition, this value is obtained by taking 100 g of the pulverized product and selecting 20 larger pulverized products and taking the average value.
[0029] [Polyester resin (B)] Polyester resin (B) (4) The polyester resin (B) is a resin containing an aluminum compound and a phosphorus compound, that is, the polyester resin (B) is produced using a polymerization catalyst composed of an aluminum compound and a phosphorus compound in a catalytic amount. Furthermore, the polyester resin (B) is a resin obtained by polycondensing a raw material of di-2-hydroxyethyl terephthalate containing a polyester resin decomposition component. In addition, di-2-hydroxyethyl terephthalate obtained by decomposing a polyester resin is sometimes referred to as chemically recycled BHET.
[0030] Chemical recycling BHET is a resin obtained by heating polyethylene terephthalate (PET) in the presence of ethylene glycol to depolymerize. The raw material PET is preferably a used article. As an example, recycled PET bottles, trays and other containers, fibers or products can be listed, as outflow products before sorting products in manufacturing, B-grade products that have not been shipped to the market, ear-shaped parts held during film stretching, cut tails, and molded products returned due to complaints, etc. The terephthalic acid and ethylene glycol of these raw materials PET can be substances derived from petroleum or substances derived from biomass. In addition, it can also be a molded product recycled by physical methods. In addition, it can also be a mixture of these PETs. These raw material PET are preferably used in the ring-opening polymerization step after being pulverized, washed, and freed of foreign matter.
[0031] BHET obtained by chemical recycling may not contain pigments, dyes, catalysts, metal ions, etc. contained in PET, and may contain linear dimers, trimers, etc. The chemically recycled PET decomposition component BHET may also contain dicarboxylic acid components other than terephthalic acid components and diol components other than ethylene glycol. Examples of dicarboxylic acid components other than terephthalic acid components include naphthalene dicarboxylic acid and isophthalic acid, and examples of diol components other than ethylene glycol include diethylene glycol, neopentyl glycol, cyclohexanedimethanol, trimethylene glycol, and tetramethylene glycol.
[0032] The chemical recycling of BHET is preferably carried out by mixing with an aluminum compound and a phosphorus compound as a polycondensation catalyst, heating under reduced pressure for polycondensation, and synthesizing PET. At this time, the lower limit of the amount of BHET for chemical recycling is preferably 50% by mass, more preferably 60% by mass, further preferably 70% by mass, particularly preferably 80% by mass, and most preferably 90% by mass, relative to the total amount of BHET. By setting it to the above, environmental adaptability (such as the ease of preparation of the polyester resin composition, the ease of preparation of the polyester film, etc.) can be improved. The amount of BHET recycled by chemical recycling may be 100% by mass relative to the total amount of BHET.
[0033] When all polycarboxylic acid component structural units are 100 mol% or all polyol component structural units are 100 mol%, the amount of structural units of dicarboxylic acid components other than the polycarboxylic acid component (preferably the terephthalic acid component) in the chemical recycling BHET, and the amount of structural units of diol components other than the polyol component (preferably the ethylene glycol component) are preferably 2 mol% or less, more preferably 1.7 mol% or less, further preferably 1.5 mol% or less, further preferably 1.0 mol% or less, particularly preferably 0.7 mol% or less, and most preferably 0.5 mol% or less. As a representative of dicarboxylic acid components other than the terephthalic acid component, isophthalic acid components can be cited, and the amount of isophthalic acid components is also as described above. As a representative of diol components other than the ethylene glycol component, diethylene glycol can be cited, and the amount of diethylene glycol components is also as described above. As described above, the chemically recycled BHET is preferably a product obtained by depolymerizing PET containing recycled products from the market. The recycled PET from the market may have components other than PET added thereto for the purpose of adjusting crystallinity and physical properties, but it is not preferred to select only pure PET from the recycled products or to purify the chemically recycled BHET until the components other than terephthalic acid and ethylene glycol are at a level that cannot be detected. Therefore, the amount of dicarboxylic acid component structural units other than terephthalic acid components and the amount of diol component structural units other than ethylene glycol in the chemically recycled BHET are preferably 0.01 mol% or more, and more preferably 0.05 mol% or more.
[0034] The polyester resin (B) may contain, in addition to BHET, at least one selected from polycarboxylic acids and ester-forming derivatives thereof, and at least one selected from polyols and ester-forming derivatives thereof.
[0035] <Polycarboxylic acid component> The main polycarboxylic acid component constituting the polyester resin (B) is preferably terephthalic acid as the main component. The amount of terephthalic acid structural units is preferably 50 mol% or more, more preferably 60 mol% or more, and further preferably 65 mol% or more in 100 mol% of all polycarboxylic acid component structural units. The terephthalic acid component is preferably a component based on chemically recycled BHET. The amount of terephthalic acid structural units derived from chemically recycled BHET in all terephthalic acid component structural units is preferably 70 mol% or more, more preferably 80 mol% or more, and even more preferably 90 mol% or more. Therefore, the polycarboxylic acid component constituting the polyester resin (B) preferably contains polycarboxylic acid component structural units other than the terephthalic acid component, and the preferred lower limit of the amount of the polycarboxylic acid component structural units is 0.007 mol% (based on: the preferred lower limit of the amount of the polycarboxylic acid component structural units other than the terephthalic acid component of chemically recycled BHET is 0.01 mol% and the preferred lower limit of the terephthalic acid structural units derived from chemically recycled BHET in the terephthalic acid component structural units is 70 mol%), and the amount of the terephthalic acid structural units in the polyester resin (B) is preferably 99.993 mol% or less of 100 mol% of all the polycarboxylic acid component structural units. When the polycarboxylic acid component structural units used in the polyester resin (B) are composed of terephthalic acid structural units and isophthalic acid structural units, the amount of the terephthalic acid structural units in the polyester resin (B) is more preferably 99.99 mol% or less, further preferably 99.95 mol% or less, and further preferably 99.90 mol% or less.
[0036] Examples of dicarboxylic acids other than terephthalic acid include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, decanedicarboxylic acid, dodecanedicarboxylic acid, tetradecanedicarboxylic acid, hexadecanedicarboxylic acid, 1,3-cyclobutanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2,5-norbornanedicarboxylic acid, and dimer acid, and saturated aliphatic dicarboxylic acids or ester-forming derivatives thereof; unsaturated aliphatic dicarboxylic acids or ester-forming derivatives thereof such as fumaric acid, maleic acid, and itaconic acid; phthalic acid, isophthalic acid, 5-(alkali metal)sulfoisophthalic acid, 2,2′-biphenyldicarboxylic acid (diphenic acid) Aromatic dicarboxylic acids such as 1,3-naphthalene dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, 4,4'-biphenyl dicarboxylic acid, 4,4'-dicarboxybiphenyl sulfone, 4,4'-biphenyl ether dicarboxylic acid, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid, pamoic acid, anthracene dicarboxylic acid, or ester-forming derivatives thereof are also included.
[0037] As polycarboxylic acids other than these dicarboxylic acids, if in small amounts, polycarboxylic acids of more than 3 valence and hydroxycarboxylic acids may also be used in combination, preferably polycarboxylic acids of 3 to 4 valence. As polycarboxylic acids, for example, ethanetricarboxylic acid, propanetricarboxylic acid, butanetetracarboxylic acid, pyromellitic acid, trimellitic acid, trimesic acid, 3,4,3',4'-biphenyltetracarboxylic acid and their ester-forming derivatives may be cited. The amount of polycarboxylic acid structural units of more than 3 valence is preferably less than 20 mol %, more preferably less than 10 mol %, and further preferably less than 5 mol % relative to the total polycarboxylic acid components. In addition, when two or more polycarboxylic acids of more than 3 valence are used in combination, it is preferred that their total amount is within the above range.
[0038] As hydroxycarboxylic acids, lactic acid, citric acid, malic acid, tartaric acid, glycolic acid, 3-hydroxybutyric acid, p-hydroxybenzoic acid, p-(2-hydroxyethoxy)benzoic acid, 4-hydroxycyclohexanecarboxylic acid or their ester-forming derivatives can be cited. The amount of the hydroxycarboxylic acid structural unit is preferably 20 mol% or less, more preferably 10 mol% or less, and further preferably 5 mol% or less relative to the total polycarboxylic acid component structural units. In addition, when two or more hydroxycarboxylic acids are used, it is preferred that their total amount is within the above range.
[0039] Examples of ester-forming derivatives of polycarboxylic acids or hydroxycarboxylic acids include their alkyl esters, acid chlorides, and acid anhydrides.
[0040] <Polyol component> The main polyol component constituting the polyester resin (B) is preferably ethylene glycol as the main component. The amount of ethylene glycol structural units is preferably 50 mol% or more and 99.99 mol% or less of all polyol component structural units 100 mol%, more preferably 60 mol% or more and 99.95 mol% or less, and further preferably 65 mol% or more and 99.90 mol% or less. The ethylene glycol component is preferably a component based on chemical recycling BHET. The ethylene glycol structural unit derived from chemical recycling BHET in all polyol component structural units is preferably 70 mol% or more, more preferably 80 mol% or more, and further preferably 90 mol% or more.
[0041] Examples of the diols other than ethylene glycol include 1,2-propylene glycol, 1,3-propylene glycol, diethylene glycol, triethylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, 1,4-butylene glycol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,2-cyclohexanediol, 1,3-cyclohexanediol, 1,4-cyclohexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, 1,10-decanediol, 1,12-decanediol, and 1,13-decanediol. Alkylene glycols such as dioxane glycol, etc.; aliphatic glycols such as polyethylene glycol, polytrimethylene glycol, polytetramethylene glycol, etc.; aromatic glycols such as hydroquinone, 4,4'-dihydroxybisphenol, 1,4-bis(β-hydroxyethoxy)benzene, 1,4-bis(β-hydroxyethoxyphenyl)sulfone, bis(p-hydroxyphenyl)ether, bis(p-hydroxyphenyl)sulfone, bis(p-hydroxyphenyl)methane, 1,2-bis(p-hydroxyphenyl)ethane, bisphenol A, bisphenol C, 2,5-naphthalene diol, and glycols obtained by adding ethylene oxide to these glycols.
[0042] Among these diols, neopentyl glycol, 1,3-propylene glycol, 1,4-butanediol or 1,4-cyclohexanedimethanol is preferred. The above-mentioned alkylene glycols may contain a substituent or an alicyclic structure in the molecular chain, and two or more thereof may be used simultaneously.
[0043] As polyols other than these diols, trivalent or higher polyols may be used in combination if the amount is small, and tri- to tetravalent polyols are preferably used in combination. Examples of trivalent or higher polyols include trimethylolmethane, trimethylolethane, trimethylolpropane, pentaerythritol, glycerol, and hexanetriol.
[0044] The trivalent or higher polyol structural unit is preferably 20 mol% or less, more preferably 10 mol% or less, and further preferably 5 mol% or less relative to the total polyol component structural units. When two or more trivalent or higher polyols are used, their total amount is preferably within the above range.
[0045] In addition, cyclic esters may also be used in combination. Examples of cyclic esters include ε-caprolactone, β-propiolactone, β-methyl-β-propiolactone, δ-valerolactone, glycolide, and lactide. In addition, examples of ester-forming derivatives of polyols include esters of polyols with lower aliphatic carboxylic acids such as acetic acid.
[0046] The cyclic ester structural unit is preferably 20 mol% or less, more preferably 10 mol% or less, and further preferably 5 mol% or less relative to the total 200 mol% of the structural units of all polycarboxylic acid components and all polyol components. In addition, when two or more cyclic esters are used, it is preferred that their total amount is within the above range.
[0047] The composition of the polyester resin (B) is determined according to the composition of the manufactured film in consideration of the composition of the polyester resin (A). For example, when the polyester resin (A) is a resin mainly composed of recycled products of beverage bottles, the main structural unit of the polyester resin (A) is ethylene terephthalate, so as long as the polyethylene terephthalate film is manufactured, the polyester resin (B) is also polyethylene terephthalate. In this case, the polyester resin (B) preferably contains 90 mol% or more of a component derived from ethylene terephthalate monomer, more preferably 95 mol% or more, and further preferably 97 mol% or more. The polyester resin (B) contains a copolymer component derived from chemically recycled BHET, and as described above, as a representative copolymer component, an isophthalic acid component can be listed. When the polyester resin (B) is polyethylene terephthalate, the preferred amount of the isophthalic acid component is the same as the preferred amount listed in the description of chemically recycled BHET. Specifically, when the polyester resin (B) is polyethylene terephthalate, when all the polycarboxylic acid component structural units are set to 100 mol%, the preferred amount of the isophthalic acid component is preferably 2 mol% or less, the second most preferred amount is 1.7 mol% or less, the further preferred amount is 1.5 mol% or less, the further preferred amount is 1.0 mol% or less, the particularly preferred amount is 0.7 mol% or less, the most preferred amount is 0.5 mol% or less, and the lower limit is preferably 0.01 mol% or more, and more preferably 0.05 mol% or more. When the polyester resin (A) is a resin mainly composed of recycled beverage bottles, the polyester resin (A) often contains isophthalic acid structural units. When the amount of the isophthalic acid structural units in the polyethylene terephthalate as the polyester resin (B) satisfies the above range, even when the mixing ratio of the polyester resin (A) to the polyester resin (B) is changed, the lamination strength, adhesion, etc. of the obtained film can be improved and made to be stable values. In addition, when the polyester resin (A) contains diethylene glycol structural units, when the amount of the diethylene glycol structural units in the polyethylene terephthalate as the polyester resin (B) satisfies the above range, even when the mixing ratio of the polyester resin (A) to the polyester resin (B) is changed, the lamination strength, adhesion, etc. of the obtained film can be made to be stable values.
[0048] On the other hand, when the film to be produced is a heat shrinkable film, a film for molding, or the like, the polyester resin (B) is preferably a copolymerized polyester resin. For example, terephthalic acid / ethylene isophthalate copolymers, ethylene terephthalate / butylene glycol copolymers, ethylene terephthalate / 2,2-dimethylpropylene glycol copolymers (neopentyl glycol is added to the glycol component), ethylene glycol / 2,2'-oxydiethylene glycol copolymers (diethylene glycol is added to the glycol component), ethylene terephthalate / 1,4-cyclohexanedimethanol copolymers (1,4-cyclohexanedimethanol is added to the glycol component), and the like, and further, products obtained by copolymerizing these with other components.
[0049] <Polymerization Catalyst> As described above, the polyester resin (B) is produced using a polymerization catalyst composed of an aluminum compound and a phosphorus compound.
[0050] (Aluminum compounds) The aluminum compound constituting the polymerization catalyst of the polyester resin (B) is not limited as long as it is soluble in a solvent, and a known aluminum compound can be used without limitation. Examples of the aluminum compound include carboxylates such as aluminum formate, aluminum acetate, basic aluminum acetate, aluminum propionate, aluminum oxalate, aluminum acrylate, aluminum laurate, aluminum stearate, aluminum benzoate, aluminum trichloroacetate, aluminum lactate, aluminum citrate, aluminum tartrate, and aluminum salicylate; inorganic acid salts such as aluminum chloride, aluminum hydroxide, hydroxyaluminum chloride, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum phosphate, and aluminum phosphonate; aluminum alkoxides such as aluminum methoxide, aluminum ethoxide, aluminum n-propoxide, aluminum isopropoxide, aluminum n-butoxide, and aluminum tert-butoxide; chelates such as aluminum acetylacetonate, aluminum ethyl acetoacetate, and ethylaluminum diisopropyl acetoacetate; organic aluminum compounds such as trimethylaluminum and triethylaluminum and partial hydrolyzates thereof, reaction products of aluminum alkoxides or aluminum chelates with hydroxycarboxylic acids, aluminum oxide, ultrafine aluminum oxide, aluminum silicate, and composite oxides of aluminum with titanium or silicon, zirconium, alkali metals, alkaline earth metals, and the like. Among them, at least one selected from carboxylates, inorganic acid salts and chelates is preferred, at least one selected from aluminum acetate, basic aluminum acetate, aluminum chloride, aluminum hydroxide, hydroxyaluminum chloride and aluminum acetylacetonate is more preferred, at least one selected from aluminum acetate, basic aluminum acetate, aluminum chloride, aluminum hydroxide, hydroxyaluminum chloride and aluminum acetylacetonate is further preferred, at least one selected from aluminum acetate and basic aluminum acetate is particularly preferred, and basic aluminum acetate is most preferred.
[0051] The aluminum compound is preferably soluble in a solvent such as water or glycol. The solvent that can be used in the production of the polyester resin (B) is preferably water and alkylene glycols. Among the alkylene glycols, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, trimethylene glycol, ditrimethylene glycol, tetramethylene glycol, ditetramethylene glycol, neopentyl glycol, etc. can be cited. Preferably, it is at least one selected from water, ethylene glycol, trimethylene glycol, and tetramethylene glycol, and more preferably water or ethylene glycol.
[0052] Polyester resin (B) (5) The content of aluminum in the polyester resin (B) is preferably 5 to 50 mass ppm, more preferably 7 to 40 mass ppm, further preferably 10 to 30 mass ppm, and particularly preferably 15 to 25 mass ppm. When the aluminum content is less than 5 mass ppm, the polymerization activity may not be fully exerted. On the other hand, when it is greater than 50 mass ppm, the amount of aluminum-based foreign matter may increase.
[0053] In addition, when cost is important, the content of aluminum in the polyester resin (B) is preferably 9 to 20 mass ppm, more preferably 9 to 19 mass ppm, further preferably 10 to 17 mass ppm, and particularly preferably 12 to 17 mass ppm. When the aluminum content is less than 9 mass ppm, the polymerization activity may not be fully exerted. On the other hand, when it is greater than 20 mass ppm, the amount of aluminum-based foreign matter may increase due to the relationship with the content of phosphorus described below, and the cost of the catalyst increases. The polyester resin (B) may be one kind or a combination of two or more kinds. When two or more kinds of polyester resins (B) are used, the content of the above-mentioned aluminum element may be an average value satisfying the above-mentioned range. In this case, an aluminum element having a content outside the above-mentioned range may also be used. The content of aluminum element is measured by the method described in the following examples, for example.
[0054] (Phosphorus compounds) The phosphorus compound constituting the polymerization catalyst of the polyester resin (B) is not particularly limited, but is preferably a phosphonic acid compound or a phosphinic acid compound from the viewpoint of a greater effect of improving the catalytic activity. Among them, a phosphonic acid compound is more preferred from the viewpoint of a particularly great effect of improving the catalytic activity.
[0055] Among the above-mentioned phosphorus compounds, phosphorus compounds having a phosphorus element and a phenol structure in the same molecule are preferred. There are no particular limitations on the phosphorus compound as long as it has a phosphorus element and a phenol structure in the same molecule. From the viewpoint of a greater effect of improving the catalytic activity, it is preferably one or more compounds selected from phosphonic acid compounds having a phosphorus element and a phenol structure in the same molecule and phosphinic acid compounds having a phosphorus element and a phenol structure in the same molecule. From the viewpoint of a very large effect of improving the catalytic activity, one or more phosphonic acid compounds having a phosphorus element and a phenol structure in the same molecule are more preferred.
[0056] In addition, examples of phosphorus compounds having a phosphorus element and a phenol structure in the same molecule include: 1 (OR 2 )(OR 3 ) or P(=O)R 1 R 4 (OR 2) represented by the compound, etc. 1 R represents a hydrocarbon group having 1 to 50 carbon atoms and having a phenol structure, and a hydrocarbon group having 1 to 50 carbon atoms and having a substituent selected from a hydroxyl group, a halogen atom, an alkoxy group and an amino group and a phenol structure. 4 R represents hydrogen, a hydrocarbon group having 1 to 50 carbon atoms, and a hydrocarbon group having 1 to 50 carbon atoms having a substituent selected from a hydroxyl group, a halogen atom, an alkoxy group, and an amino group. 2 , R 3 Each independently represents hydrogen, a hydrocarbon group having 1 to 50 carbon atoms, or a hydrocarbon group having 1 to 50 carbon atoms having a substituent selected from a hydroxyl group and an alkoxy group. The hydrocarbon group may contain a branched structure, an alicyclic structure such as a cyclohexyl group, or an aromatic ring structure such as a phenyl group or a naphthyl group. 2 and R 4 The ends of the nucleotides may also be bonded.
[0057] As the phosphorus compound having a phosphorus element and a phenol structure in the same molecule, for example, p-hydroxyphenylphosphonic acid, dimethyl p-hydroxyphenylphosphonic acid, diethyl p-hydroxyphenylphosphonic acid, diphenyl p-hydroxyphenylphosphonic acid, bis(p-hydroxyphenyl)phosphinic acid, methyl bis(p-hydroxyphenyl)phosphinic acid, phenyl bis(p-hydroxyphenyl)phosphinic acid, p-hydroxyphenylphosphinic acid, methyl p-hydroxyphenylphosphinic acid, phenyl p-hydroxyphenylphosphinic acid, and the like.
[0058] As the phosphorus compound having a phosphorus element and a phenol structure in the same molecule, in addition to the above examples, there can be cited phosphorus compounds having a phosphorus element and a hindered phenol structure (a phenol structure in which an alkyl group having a tertiary carbon is bonded to one or two ortho positions of a hydroxyl group, and the alkyl group having a tertiary carbon is preferably an alkyl group having a tertiary carbon at a benzylic carbocation, such as tert-butyl, 1,1,2-trimethylpropyl, neopentyl, etc.) in the same molecule. Preferably, the phosphorus compound having a phosphorus element and a structure of the following (chemical formula A) in the same molecule is preferred, and 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester shown in the following (chemical formula B) is more preferred. In addition, as the phosphorus compound used in the production of the polyester resin (B), 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester shown in the following (chemical formula B) is preferred, and in addition to these, a modified body of 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester may be contained. The details of the modified body are described below.
[0059]
[0060] (In the chemical formula A, * represents the chemical compound P(=O)R 1 (OR 2 )(OR 3 ) 1 The chemical bond of the hydrocarbon group.
[0061]
[0062] ((Chemical Formula B) where X 1 , X 2 represents hydrogen or an alkyl group having 1 to 4 carbon atoms.)
[0063] In this specification, at least one hindered phenol structure can be detected by the P-NMR measurement method of a solution of a polyester resin dissolved in a hexafluoroisopropanol-based solvent. A polyester resin in which a hindered phenol structure is detected is also referred to as a "hindered phenol structure-containing" polyester resin. That is, the polyester resin (B) is preferably a polyester resin produced using a phosphorus compound having a phosphorus element and a hindered phenol structure in the same molecule as a polymerization catalyst. The method for detecting the hindered phenol structure in the polyester resin (B) (P-NMR measurement method) is described below.
[0064] In the above (chemical formula B), X 1 , X 2 All of them are preferably alkyl groups having 1 to 4 carbon atoms, and more preferably alkyl groups having 1 to 2 carbon atoms. In particular, ethyl esters having 2 carbon atoms are preferred because they are commercially available as Irganox 1222 (manufactured by BASF) and are easily available.
[0065] The phosphorus compound is preferably used after heat treatment in a solvent. In addition, the details of the heat treatment are described below. As the phosphorus compound, when the phosphorus compound 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester shown in the above (chemical formula B) is used, it is preferred that in the above heat treatment, a part of the structure of the phosphorus compound 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester shown in (chemical formula B) changes. For example, at least one of the detachment of the tert-butyl group, the hydrolysis of the ethyl ester group and the hydroxyethyl ester exchange structure (ethylene glycol and ester exchange structure) may occur. Therefore, in the present invention, as a phosphorus compound, in addition to the 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester shown in (chemical formula B), a phosphorus compound with a changed structure may also be contained. In addition, the detachment of the tert-butyl group occurs significantly at high temperatures in the polymerization process.
[0066] The following are nine phosphorus compounds in which a part of the structure of diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate is changed when diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate is used as the phosphorus compound. The amount of each phosphorus compound in which the structure is changed in the diol solution can be quantified by the P-NMR measurement method.
[0067]
[0068] Therefore, the phosphorus compound in the present invention may contain 9 types of modified forms of dialkyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate represented by the above chemical formula in addition to dialkyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate.
[0069] When Irganox 1222 is used as the phosphorus compound, the polyester resin may contain 9 types of phosphorus compound residues as shown in Table 1 below. When at least one of the 9 types of hindered phenol structures shown in Table 1 is detected by the P-NMR measurement method, it can be said that the polyester resin (B) is a polyester resin produced using a phosphorus compound having a phosphorus element and a hindered phenol structure in the same molecule as a polymerization catalyst. By using a phosphorus compound having a hindered phenol structure, sufficient polymerization activity can be exerted while suppressing the cost of the catalyst.
[0070]
Table 1
[0071] In the present invention, it is preferred that at least one of the above Chemical Formulas 1, 4 and 7 is contained.
[0072] Polyester resin (B) (6) The phosphorus content in the polyester resin (B) is preferably 5 to 1000 mass ppm, more preferably 10 to 500 mass ppm, further preferably 15 to 200 mass ppm, particularly preferably 20 to 100 mass ppm, and most preferably 30 to 50 mass ppm. When the phosphorus content is less than 5 mass ppm, the polymerization activity may decrease and the amount of aluminum-based foreign matter may increase. On the other hand, when it is greater than 1000 mass ppm, the polymerization activity may decrease, the amount of phosphorus compound added may increase, and the catalyst cost may increase.
[0073] When cost is more important, the phosphorus content in the polyester resin (B) is preferably 13 to 31 mass ppm, more preferably 15 to 29 mass ppm, and further preferably 16 to 28 mass ppm. When the phosphorus content is less than 13 mass ppm, the polymerization activity may decrease and the amount of aluminum-based foreign matter may increase. On the other hand, when it is greater than 31 mass ppm, the polymerization activity may decrease, the amount of phosphorus compound added may increase, and the catalyst cost may increase. The polyester resin (B) may be one kind or a combination of two or more kinds. When two or more kinds of polyester resins (B) are used, the phosphorus content may be an average value. In this case, a phosphorus content greater than the above range may be used. The phosphorus content can be measured, for example, by the method described in the following Examples.
[0074] In the polyester resin (B), the molar ratio of phosphorus to aluminum (hereinafter referred to as "residual molar ratio of phosphorus to aluminum" to distinguish it from the "added molar ratio of phosphorus to aluminum" described below) is preferably 1.00 to 5.00, more preferably 1.10 to 4.00, further preferably 1.20 to 3.50, and particularly preferably 1.25 to 3.00. As described above, the aluminum and phosphorus in the polyester resin (B) are derived from the aluminum compound and phosphorus compound used as the polymerization catalyst of the polyester resin (B), respectively. By using these aluminum compounds and phosphorus compounds in combination at a specific ratio, a coordination compound having catalytic activity is formed in the polymerization system, and sufficient polymerization activity can be exerted. In addition, the resin produced using a polymerization catalyst composed of an aluminum compound and a phosphorus compound has a higher catalyst cost (higher production cost) than a polyester resin produced using a catalyst such as an antimony catalyst, but by using an aluminum compound and a phosphorus compound in combination at a specific ratio, sufficient polymerization activity can be exerted while suppressing the catalyst cost. When the residual molar ratio of phosphorus to aluminum is less than 1.00, thermal stability and thermal oxidation stability may decrease, and the amount of aluminum-based foreign matter may increase. On the other hand, when the residual molar ratio of phosphorus to aluminum is greater than 5.00, the amount of phosphorus compound added becomes too much, and the catalyst cost may increase. When cost is given priority, the residual molar ratio of phosphorus element to aluminum element is preferably 1.32 to 1.80, and more preferably 1.38 to 1.68.
[0075] As the polymerization catalyst used in the manufacture of the polyester resin (B), in addition to the above-mentioned aluminum compounds and phosphorus compounds, other polymerization catalysts such as antimony compounds, germanium compounds, and titanium compounds may also be used in combination within the range that the characteristics, processability, color tone, etc. of the polyester resin (B) do not cause problems in the product. The content of antimony element in the polyester resin (B) is preferably 30 mass ppm or less, the content of germanium element in the polyester resin (B) is preferably 10 mass ppm or less, and the content of titanium element in the polyester resin (B) is preferably 3 mass ppm or less. Among them, it is preferred not to use the above-mentioned other condensation catalysts as much as possible, and it is more preferred that the content of other condensation catalysts is as much as possible 0 mass ppm. In addition, it is not excluded that a trace amount of other polymerization catalysts are mixed in due to residual resin in the manufacturing device of the polyester resin (B).
[0076] The content of aluminum elements corresponding to aluminum-based foreign matters in the polyester resin (B) is preferably 3000 mass ppm or less, more preferably 2800 mass ppm or less, further preferably 2000 mass ppm or less, and further preferably 1500 mass ppm or less. Aluminum-based foreign matters refer to foreign matters derived from aluminum compounds used as polymerization catalysts, which are foreign matters insoluble in the polyester resin (B). When the content of aluminum-based foreign matters is greater than the above, they become the cause of fine foreign matters insoluble in the polyester resin (B), and the quality of the molded body may deteriorate. In addition, in the polycondensation process and the molding process, the filter clogging during polyester filtration may increase. The preferred lower limit of the content of aluminum elements corresponding to aluminum-based foreign matters is preferably 0 mass ppm, but due to technical difficulties, it is about 300 mass ppm. In addition, in this specification, it can be understood that the aluminum element amount is measured by the following measurement method in the examples. This index is an index for relatively evaluating the aluminum foreign matter amount based on the aluminum element amount, and does not represent the absolute value of the aluminum foreign matter amount contained in the polyester resin.
[0077] The intrinsic viscosity of the polyester resin (B) is preferably 0.50 to 0.90 dl / g, more preferably 0.55 to 0.80 dl / g, and further preferably 0.58 to 0.75 dl / g. When the intrinsic viscosity of the polyester resin (B) is less than the above, a large amount of fine powder (fine) may be generated due to friction between the polyester resin particles and between the polyester resin particles and the pneumatic transport pipe during pneumatic transport of the polyester resin (B). When the intrinsic viscosity of the polyester resin (B) is greater than the above, when the polyester resin (B) is melt-mixed with the recycled polyester resin (A), the local shear heating may increase, causing the resin to deteriorate, and the stress during stretching may increase, making the production of the film difficult. The intrinsic viscosity of the polyester resin (B) can be adjusted according to the intrinsic viscosity of the polyester resin (A) so that the intrinsic viscosity of the polyester constituting the film is within an appropriate range. Furthermore, when a polyester resin (B) having an intrinsic viscosity greater than 0.62 dl / g is produced only by melt polymerization, economic efficiency may decrease. Therefore, when a polyester resin (B) greater than 0.62 dl / g is required, it is preferred to polymerize the polyester resin (B) obtained by melt polymerization by a solid phase polymerization method.
[0078] When solid phase polymerization is performed, the CT content in the polyester resin (B) is preferably 7000 mass ppm or less, more preferably 6000 mass ppm or less, and further preferably 5500 mass ppm or less. In practice, the CT content is preferably 2500 mass ppm or more, more preferably 3000 mass ppm or more, further preferably 3500 mass ppm or more, and further preferably 4000 mass ppm or more.
[0079] The intrinsic viscosity retention rate of the polyester resin (B) is preferably higher than that of the polyester resin (A). In the present invention, the intrinsic viscosity retention rate of the entire polyester resin composition is increased by mixing the polyester resin (B) having a high intrinsic viscosity retention rate with the polyester resin (A) having a low intrinsic viscosity retention rate. The intrinsic viscosity retention rate of the polyester resin (B) is preferably 93% or more, more preferably 94% or more, and further preferably 95% or more. When the intrinsic viscosity retention rate of the polyester resin (B) is less than 93%, the intrinsic viscosity retention rate of the polyester resin composition (C) becomes low, and the recycling property may become insufficient. The upper limit of the intrinsic viscosity retention rate of the polyester resin (B) is preferably 100%, but due to technical difficulties, it is about 99%. The intrinsic viscosity retention rate of the polyester resin (B) means the intrinsic viscosity retention rate of a sample after one remilling, and can be measured as follows.
[0080] In addition, the production method of the polyester resin (B) is as follows. The polyester resin (B) is preferably prepared into pellets in which the longest distance between any two points is preferably 2 to 10 mm, more preferably 3 to 6 mm. Examples of the shape of the pellets include spherical, ellipsoidal, cylindrical, and cubic shapes.
[0081] The polyester resin (B) may be a resin pelletized after polymerization, or may be a product recovered during the process of molding an article using the polyester resin (B). Examples of the products recovered during the process include products that are not shipped to the market as B-grade products, ear-shaped parts held during film stretching, cut tails, and molded products returned due to complaints, etc. In the case of these products recovered during the process, they are preferably crushed products similar to the polyester resin (A).
[0082] The polyester resin (B) can also be used as a masterbatch (concentrated resin) of additives like the polyester resin (D) described below.
[0083] [Polyester resin composition (C)] In the present invention, polyester resin (A) and polyester resin (B) are mixed to produce a film. The resin formed by mixing polyester resin (A) and polyester resin (B) is called polyester resin composition (C). In the production of the film, polyester resin (A) and polyester resin (B) can be fed into the extruder from different feed ports, or from the same feed port, or after dry mixing the two in advance. For the sake of handling, preferably, the mixing step of polyester resin (A) and polyester resin (B) includes preparing polyester resin composition (C) by melt mixing polyester resin (A) and polyester resin (B). It is preferably used for the production of the film. Preferably, the polyester resin (A) and the polyester resin (B) are mixed at a mass ratio of 5:95 to 95:5 to produce the polyester resin composition (C). That is, preferably, in the polyester resin composition (C), the content of the polyester resin (A) is 5 to 95 parts by mass relative to 100 parts by mass of the total of the polyester resin (A) and the polyester resin (B). By setting it within the above range, the coloring and molecular weight reduction of the polyester resin composition (C) can be suppressed. In addition, the suppression of coloring in this specification means that even if the number of recycling times is multiple times (repeated re-milling), the following L value reduction and the following b value increase are suppressed. When the content of the polyester resin (A) is greater than 95 parts by mass, the intrinsic viscosity retention rate of the polyester resin composition (C) becomes low, and the recycling efficiency may become insufficient. On the other hand, when the content of the polyester resin (A) is less than 5 parts by mass, the coloring suppression effect is saturated and the economic efficiency may decrease. In addition, since the polyester resin (B) is produced using a polymerization catalyst composed of an aluminum compound and a phosphorus compound, even if the residual molar ratio of phosphorus element to aluminum element is within the above-mentioned specified range, the cost of the catalyst is increased (the manufacturing cost is increased) compared with the polyester resin produced using a catalyst such as an antimony catalyst, but by using the polyester resin (A) and the polyester resin (B) in combination, the recycling efficiency can be improved while suppressing the manufacturing cost. When the content of the polyester resin (A) is increased, the manufacturing cost of the polyester resin composition (C) can be suppressed, but the color tone becomes easily deteriorated when the number of recycling times is multiple. On the other hand, when the content of the polyester resin (B) is increased, the deterioration of the color tone can be suppressed even if the number of recycling times of the polyester resin composition (C) is multiple, but the manufacturing cost may increase. The mass ratio of the polyester resin (A) to the polyester resin (B) is more preferably 20:80 to 80:20, and further preferably 25:75 to 75:25.
[0084] The polyester resin (A) and the polyester resin (B) may be dry mixed to produce the polyester resin composition (C). In addition, the polyester resin (A) and the polyester resin (B) may be mixed by melt extrusion to produce the polyester resin composition (C). In this case, the polyester resin (A) and the polyester resin (B) are mixed separately or dry mixed, and then put into a common resin mixing device such as a Banbury mixer, a kneader, a single screw extruder, a twin screw extruder, a four screw extruder, a single screw planetary extruder, etc., and the polyester resin composition (C) is produced by melting / mixing. Among them, preferred are extruders with excellent surface renewal properties such as twin-screw extruders, quad-screw extruders, and single-screw planetary extruders. In addition, the extruder has at least one, preferably two, and more preferably three exhaust ports, and a preferred embodiment is that the exhaust port is connected to a decompression system to suppress the degradation of the polyester resin composition (C). After the polymerization of the polyester resin (B) is completed, the polyester resin (A) may be added to the molten polyester resin (B) before being cooled and pelletized, and kneaded to form a polyester resin composition (C).
[0085] The polyester resin composition (C) may be directly formed into a film in a molten state, but is preferably pelletized in advance. The shape of the pellets is the same as that of the polyester resin (B).
[0086] The intrinsic viscosity of the polyester resin composition (C) is preferably 0.50 to 0.90 dl / g, more preferably 0.55 to 0.80 dl / g, and further preferably 0.58 to 0.75 dl / g. When the intrinsic viscosity of the polyester resin composition (C) is less than the above, the mechanical strength and impact resistance of the manufactured polyester film may become insufficient. When the intrinsic viscosity of the polyester resin composition (C) is greater than the above, the economic efficiency may decrease, the local shear heat generated during melting in the extruder may increase, causing the resin to deteriorate, and the stress during stretching may increase, making the film production difficult.
[0087] The intrinsic viscosity retention rate of the polyester resin composition (C) is preferably 89% or more, more preferably 90% or more, further preferably 92% or more, particularly preferably 93% or more, and most preferably 94% or more. When the intrinsic viscosity retention rate of the polyester resin composition (C) is less than 89%, the recycling efficiency may become insufficient. The upper limit of the intrinsic viscosity retention rate of the polyester resin composition (C) is preferably 100%, but due to technical difficulties, it is about 99%. In addition, the intrinsic viscosity retention rate of the polyester resin composition (C) is preferably higher than the intrinsic viscosity retention rate of the polyester resin (A). In addition, in this specification, when simply described as "intrinsic viscosity retention rate", it refers to the intrinsic viscosity retention rate of the re-refined product that has been re-refined only once. That is, the intrinsic viscosity retention rate of the polyester resin (A), the polyester resin (B), the polyester resin (C), the polyester resin (D), and the polyester resin composition (E) can be measured as follows. Intrinsic viscosity retention rate (%) = Intrinsic viscosity of the sample after 1 re-melting / Intrinsic viscosity of the sample × 100 (The first remilled sample is a sample that has passed through a twin-screw extruder under the conditions of a temperature of 260°C, a screw speed of 200 rpm, and an output of 1.7 to 2.0 kg / h. The intrinsic viscosity is calculated by feeding a solution of 0.2 g of the sample and 20 ml of a mixed solvent of 1,1,2,2-tetrachloroethane and p-chlorophenol (mass ratio 1:3) to an Ubbelohde viscometer at 30°C.)
[0088] The CT content contained in the re-refined product of the polyester resin composition (C) after the first re-refining is preferably 6600 mass ppm or less, more preferably 6400 mass ppm or less, and further preferably 6000 mass ppm or less. The lower limit is not limited, but due to technical difficulties, it is about 2500 mass ppm, preferably 3000 mass ppm or more. When the CT content is greater than 6600 mass ppm, the amount of CT precipitation on the film surface increases, the haze increases, etc., which is sometimes not preferred depending on the application, and there is a possibility that the film manufacturing equipment is contaminated by CT, and the number of cleaning times needs to be increased. In order to set the CT content of the polyester resin composition (C) to the above or below, there are methods such as using a resin with a small CT content of the polyester resin (A), reducing the CT content of the polyester resin (B), and reducing the CT content of the polyester resin composition (C). As a method for reducing the CT content of the polyester resin (B) and the polyester resin composition (C), there are methods such as solid phase polymerization, heating treatment at 190 to 220° C. in a closed container or in an air flow containing ethylene glycol.
[0089] The value (ΔCT) obtained by subtracting the CT amount of the re-refined product of the polyester resin composition (C) re-refined once from the CT amount of the re-refined product of the polyester resin composition (C) re-refined three times is preferably 900 mass ppm or less, more preferably 700 mass ppm or less, and further preferably 600 mass ppm or less. The lower limit is preferably 0 mass ppm, but due to technical difficulties, it is about 200 mass ppm. When ΔCT is greater than 900 mass ppm, the amount of CT precipitated onto the film surface may increase as described above.
[0090] Furthermore, when the polyester resin composition (C) contains the polyester resin (B) produced using the above-mentioned Irganox 1222 as the phosphorus compound, when the polyester resin composition (C) is subjected to the P-NMR measurement method, at least one of the nine hindered phenol structures shown in Table 1 can be detected. The same applies to the case where a phosphorus compound having a phosphorus element and a hindered phenol structure in the same molecule other than Irganox 1222 is used as a polymerization catalyst.
[0091] [Polyester resin (D)] When producing a film according to the present invention, it is also a preferred mode to produce a polyester film by adding a polyester resin (D) different from the polyester resin (A) and the polyester resin (B). That is, the step of mixing the polyester resin (A) and the polyester resin (B) may include further mixing a polyester resin (D) different from the polyester resin (A) and the polyester resin (B). The polyester resin (D) is preferably different from the polyester resin (A) and the polyester resin (B) in one or more aspects such as constituent components, amounts of constituent components, catalysts, intrinsic viscosity, CT amount, additives, etc. The polyester resin (D) may have various compositions depending on the film to be produced. For example, when a polyethylene terephthalate film is produced, the total amount of copolymer components other than the terephthalic acid component and the ethylene glycol component in the polyester resin (D) is preferably 10 mol % or less, more preferably 7 mol % or less, and particularly preferably 5 mol % or less. For example, when a polyester-based heat shrinkable film is produced, it is preferred that the composition other than copolyester or polyethylene terephthalate be used so as to obtain the final composition of the heat shrinkable film together with the polyester resin (A) and the polyester resin (B). For example, when a polyester film containing voids is produced, the polyester may be copolymerized with polyethylene glycol, polytetramethylene glycol, or the like. The dicarboxylic acid component and the diol component used in the polyester resin (D) are the same as those exemplified in the polyester resin (B).
[0092] The intrinsic viscosity of the polyester resin (D) varies depending on the film to be produced, but is preferably 0.50 to 0.90 dl / g, more preferably 0.55 to 0.80 dl / g, and even more preferably 0.58 to 0.75 dl / g. The catalyst used for the polyester resin (D) is preferably the catalyst exemplified for the production of the polyester resin (A). The intrinsic viscosity retention rate of the polyester resin (D) is preferably high, but the intrinsic viscosity retention rate may be 92% or less or 91% or less, further may be 90% or less, and particularly may be 89% or less. The intrinsic viscosity retention rate of the polyester resin (D) can be improved by reducing the amount of the catalyst, deactivating the catalyst, adding a deterioration inhibitor such as a heat stabilizer, etc. The lower limit of the intrinsic viscosity retention rate of the polyester resin (D) is preferably the same as that of the polyester resin (A).
[0093] In the manufacture of the film, colorants, lubricant particles, ultraviolet absorbers, melt resistivity regulators, antistatic agents, antioxidants, thermal stabilizers, etc. are often added, and the polyester resin (D) can also be a masterbatch (concentrated resin) of these additives. As lubricant particles, inorganic particles such as silica, calcium carbonate, talc, kaolin, and organic particles such as cross-linked styrene, cross-linked acrylic resin, and melamine resin can be listed. As a particle size, it is preferably 10nm to 5μm, and more preferably 50nm to 3μm. The particle size can be obtained by the Coulter counter method. As a melt resistivity regulator, a combination of metal compounds such as calcium, magnesium, and potassium and phosphorus compounds can be listed.
[0094] The polyester resin (D) may be used alone or in combination of two or more. The content of the polyester resin (D) is preferably 5 to 95 parts by mass, more preferably 90 parts by mass or less, further preferably 80 parts by mass or less, further preferably 70 parts by mass or less, particularly preferably 60 parts by mass or less, and most preferably 50 parts by mass or less, relative to 100 parts by mass of the total amount of the polyester resin (A), the polyester resin (B) and the polyester resin (D). If the content is greater than the above, the recycling efficiency of the recycled polyester resin may be reduced.
[0095] [Polyester resin composition (E)] The polyester film is formed into a film by melt-mixing the polyester resin (A) and the polyester resin (B) or the polyester resin composition (C), and if necessary, the polyester resin (D) as raw material polyester resins, and forming the film by a conventional method. One embodiment of the method for producing the polyester film of the present invention comprises the step of mixing a polyester resin composition (C) which is a molten mixture of a recovered polyester resin (A) and a polyester resin (B) containing an aluminum compound and a phosphorus compound with a polyester resin (D) different from the polyester resin (A) and the polyester resin (B).
[0096] As described above, the polyester resin constituting the film is the polyester resin composition (E). In the case of a polyester film having a multilayer structure as described below, the polyester resin constituting the layer containing the polyester resin (A) and the polyester resin (B) is the polyester resin composition (E). When the polyester resin (D) is not used, the polyester resin composition (C) is the polyester resin composition (E). The composition and intrinsic viscosity of the polyester resin composition (E) are the same as those described for the polyester resin (D).
[0097] At least one polyester resin (preferably the polyester resin (A) and the polyester resin (B)) contained in the polyester resin composition (E) constituting the film preferably contains an isophthalic acid structural unit as a copolymerization component. When all polycarboxylic acid component structural units are taken as 100 mol%, the lower limit of the content of the isophthalic acid structural units in the polyester resin composition (E) is preferably 0.02 mol%, more preferably 0.05 mol%, further preferably 0.1 mol%, particularly preferably 0.2 mol%, and most preferably 0.3 mol%. The upper limit is preferably 5.0 mol%, more preferably 4.0 mol%, further preferably 3.0 mol%, particularly preferably 2.5 mol%, and most preferably 2.0 mol%. The polyester resin composition (E) constituting the film preferably contains at least antimony element, germanium element, phosphorus element and aluminum element.
[0098] The content of antimony in the polyester resin composition (E) is preferably 10 mass ppm or more, more preferably 15 mass ppm or more, and further preferably 20 mass ppm or more. The content of antimony in the polyester resin composition (E) is preferably 250 mass ppm or less, more preferably 200 mass ppm or less, and further preferably 180 mass ppm or less. By setting the content within the above range, a film with less degradation, higher transparency, and lower haze can be produced while ensuring economic efficiency.
[0099] The content of germanium in the polyester resin composition (E) is preferably 0.1 mass ppm or more, more preferably 0.15 mass ppm or more, and further preferably 0.20 mass ppm or more. The content of germanium in the polyester resin composition (E) is preferably 5 mass ppm or less, more preferably 4 mass ppm or less, and further preferably 3 mass ppm or less. By setting it to the above range, a film with less deterioration can be made while ensuring economic efficiency.
[0100] The content of aluminum in the polyester resin composition (E) is preferably 1 mass ppm or more and 20 mass ppm or less. From the viewpoint of further suppressing the reduction of coloration and further improving the intrinsic viscosity retention rate, it is more preferably 3 mass ppm or more and 20 mass ppm or less, and further preferably 5 mass ppm or more and 20 mass ppm or less. The content of aluminum in the polyester resin composition (E) may also be 17 mass ppm or less or 15 mass ppm or less. By setting it in the above range, a film with less deterioration can be produced while ensuring economic efficiency.
[0101] The CT content in the polyester resin composition (E) is preferably 6600 mass ppm or less, more preferably 6400 mass ppm or less, and may be 6000 mass ppm or less. The CT content in the polyester resin composition (E) is preferably 3000 mass ppm or more, more preferably 4000 mass ppm or more.
[0102] The ratio of the amount of antimony element to the amount of aluminum element in the polyester resin composition (E) (the content ratio of antimony element / aluminum element) is preferably 0.5 or more and 200 or less, more preferably 0.7 or more and 190 or less, and further preferably 0.9 or more and 180 or less, based on mass. The content ratio of antimony element / aluminum element may be 5 to 170, 18 to 150, or 10 to 130. By setting the content ratio within the above range, a film with less degradation, higher transparency, and lower haze can be obtained while ensuring economic efficiency. From the viewpoint of further suppressing the reduction of coloration and further improving the intrinsic viscosity retention rate, the content ratio of antimony element / aluminum element is more preferably 1 or more and 100 or less or 80 or less, particularly preferably 1 or more and 50 or less, and most preferably 1 or more and 30 or less.
[0103] The ratio of the amount of antimony element in the polyester resin composition (E) to the amount of aluminum element and phosphorus element (preferably phosphorus element derived from the polyester resin (B)) (content ratio of antimony element / (aluminum element and phosphorus element (preferably phosphorus element derived from the polyester resin (B)))) is preferably 0.1 or more and 100 or less, more preferably 0.15 or more and 90 or less, further preferably 0.2 or more and 80 or less, and further preferably 0.25 or more and 70 or less on a mass basis. By setting it within the above range, a film with less deterioration, high transparency and low haze can be obtained while ensuring economic efficiency. From the viewpoint of further suppressing the reduction of coloration and further improving the intrinsic viscosity retention rate, the content ratio of antimony element / (aluminum element and phosphorus element (preferably phosphorus element derived from the polyester resin (B))) is more preferably 0.2 or more and 50 or less, or 25 or less, particularly preferably 0.3 or more and 20 or less, and most preferably 0.3 or more and 15 or less.
[0104] The intrinsic viscosity retention rate of the polyester resin composition (E) is preferably 89% or more, more preferably 90% or more, and may be 91% or more, 92% or more, or 93% or more. The intrinsic viscosity retention rate of the polyester resin composition (E) is preferably 100%, but in practice is preferably 99% or less, more preferably 98% or less. The method for measuring the intrinsic viscosity retention rate of the polyester resin (E) is as described above.
[0105] Various properties of the polyester resin composition (E) are the same as those described with respect to the polyester resin composition (C).
[0106] The film may contain various additives in addition to the polyester resin, depending on its use or required characteristics. As additives, in addition to the various additives listed in the polyester resin (D), resins such as polyamide, polyimide, polycarbonate, polyurethane, polyether, polyphenylene sulfide, polyphenylene sulfide, polyetherimide, and polyphenylene ether may be added. If it is a polyester film containing holes, pore-forming agents such as polystyrene or polyolefin may also be added. The amount of the resins other than these polyesters added is preferably 1 to 30% by mass, more preferably 2 to 20% by mass, relative to the total amount of the polyester resin composition (E) and the resins other than the polyester resin composition (E).
[0107] [Polyester film] The polyester film of the present invention is composed of a polyester resin composition (E) containing a recycled polyester resin (A) and a polyester resin (B) containing an aluminum compound and a phosphorus compound.
[0108] The polyester film may be an unstretched film by melt-kneading in an extruder and then extruding it from a die onto a cooling roll into a thin film. Alternatively, the film may be formed by a calender method. In the case of a stretched film, the unstretched film obtained as described above may be stretched in the longitudinal direction or the width direction to obtain a uniaxially stretched or biaxially stretched polyester film.
[0109] The stretching method, for example, can be stretched between rollers with a peripheral speed difference when stretching in the length direction. For example, the width direction stretching can be held by a clamp (clip) moving along the two ends of the film width and introduced into a tenter (tenter), and stretched by widening the moving track width of the clamp. In the case of successive biaxial stretching, stretching in any direction can be performed first, but usually the length direction is stretched first. In addition, it is also possible to stretch in the length direction and the width direction simultaneously or in any order on a biaxial stretching machine. Stretching can be multi-stage stretching, and in the case of multi-stage, the length direction and the width direction can also be alternately performed.
[0110] The stretching temperature is preferably in the range of the glass transition temperature (Tg) of the polyester resin composition (E) + 5 to Tg + 70°C, and more preferably in the range of Tg + 10 to Tg + 60°C. The stretching ratio is preferably 10 times or less in at least one direction, more preferably 8 times or less, and more preferably 6 times or less. In order to impart stronger orientation, the stretching ratio is preferably 2 times or more, more preferably 2.5 times or more, and particularly preferably 2.8 times or more. Even if biaxial stretching is performed, if a film with strong uniaxiality is formed, the stretching ratio in the direction perpendicular to the main stretching direction may be less than the above.
[0111] The stretched polyester film is preferably heat-set at a temperature below the crystalline melting point (mp) of the polyester resin composition (E). The heat-setting temperature is preferably mp-10°C or less, more preferably mp-20°C or less. The lower limit of the heat-setting temperature also depends on the composition of the polyester resin composition (E) and the heat resistance required for the film, but is usually preferably 100°C or more, more preferably 130°C or more. For example, if the polyester resin composition (E) is a polyethylene terephthalate film, the heat-setting temperature is preferably 170 to 250°C, more preferably 180 to 240°C.
[0112] Heat setting is preferably performed while maintaining the stretching ratio, but in order to reduce the thermal shrinkage of the polyester film, it may be subjected to a relaxation process from heat setting to cooling, and may be shrunk by about 1 to 5% from the stretched state. The temperature of the relaxation process is preferably 100°C to the heat setting temperature - 5°C, more preferably 120°C to the heat setting temperature - 10°C. The relaxation rate of the polyester film is more preferably 1.5 to 4%.
[0113] The polyester film may be a single layer or a multilayer polyester film consisting of at least two layers. When it is a multilayer, at least one layer needs to be a polyester resin composition (E). Multiple layers or all layers may be a polyester resin composition (E), in which case the composition and ratio of the polyester resin (A), the polyester resin (B), and the polyester resin (D) may be different depending on the layer. In addition, when it is a multilayer polyester film, at least one layer may be a layer that does not contain the polyester resin (A). Furthermore, when it is a multilayer structure, it is also preferable to have three or more layers, with the intermediate layer being a layer of the polyester resin composition (E) and the outermost layer being a structure not containing the recycled polyester resin (A). When it is a multilayer film, the thickness of the layer of the polyester resin composition (E) is preferably 30% or more of the total thickness of the film, more preferably 50% or more, further preferably 60% or more, and particularly preferably 70% or more. If it is less than the above, the recycling efficiency of the recycled polyester resin (A) may be reduced.
[0114] The thickness of the polyester film is preferably 1 to 2000 μm, more preferably 2 to 1000 μm. It can be set to an appropriate range according to the application. For example, 20 to 150 μm for optical use, 10 to 100 μm for transfer or release film, 5 to 50 μm for general packaging film, and 200 to 1000 μm for thick objects such as trays are representative thicknesses.
[0115] <Surface treatment of polyester film> The polyester film is preferably subjected to a surface treatment in order to improve adhesion with adhesives, coating materials, inks, etc. Examples of the surface treatment include corona treatment, plasma treatment, and flame treatment.
[0116] The polyester film may be provided with an easy-adhesion layer. The resin used for the easy-adhesive layer can use polyester resin, polyurethane resin, polycarbonate resin, acrylic resin etc., preferably polyester resin, polyester polyurethane resin, polycarbonate polyurethane resin, acrylic resin. The easy-adhesive layer is preferably crosslinked. As a crosslinking agent, isocyanate compounds, melamine compounds, epoxy resins, oxazoline compounds etc. can be listed. In addition, adding water-soluble resins such as polyvinyl alcohol is also a useful means for improving the adhesion with polarizer.
[0117] The adhesive layer is formed by applying and drying a water-based coating prepared by adding these resins and, if necessary, a crosslinking agent, particles, etc. on the polyester film. Examples of the particles include the particles used in the above-mentioned substrate. The easy-adhesive layer can be provided on the stretched film offline, but is preferably provided online in the film-making process. When provided online, it can be provided before longitudinal stretching or transverse stretching, preferably applied just before transverse stretching, and dried and cross-linked by preheating, heating, and heat treatment steps using a tenter. In addition, when applying online just before longitudinal stretching using a roller, it is preferably introduced into the stretching roller after drying it with a vertical dryer after coating. The coating amount of the adhesive layer is preferably 0.01 to 1.0 g / m 2 , more preferably 0.03 to 0.5 g / m 2 .
[0118] The polyester film produced according to the present invention can be used for various purposes without limitation. For example, the polyester film can be used for substrate films of prisms or lens sheets, hard coating films, electrode substrate films of touch screens, anti-splash films, anti-reflection films, polarizer protective films, polarizing plate protective films, surface protective films of display devices or circuits, etc., release films of ceramic green sheets, etc., polarizing plate release films, transfer films, in-mold transfer films, in-mold forming films, barrier films deposited with aluminum or inorganic oxides, solar cell backsheets, circuit substrate films, flat cable substrate films, magnetic recording medium substrate films, ink ribbons, imaging films, labels, tags, films for cards, films for packaging bags, heat shrinkable films, trays, cover tapes, etc. Depending on the respective application, additives may be added to the membrane, and post-processing may be performed to impart functionality to the membrane.
[0119] [Method for producing polyester resin (B)] Next, the method for producing the polyester resin (B) is described. The method for producing the polyester resin (B) can be carried out by a method having known steps except that a polyester polymerization catalyst composed of an aluminum compound and a phosphorus compound is used as a catalyst, but preferably a polymerization catalyst is added so as to satisfy the following (5) and (6), and more preferably a polymerization catalyst is added so as to satisfy the following (7) in addition to the following (5) and (6). In addition, the preferred numerical ranges of the following (5) to (7) are as described above. (5) The content of aluminum in the polyester resin (B) is 5 to 50 ppm by mass (6) The phosphorus content in the polyester resin (B) is 5 to 1000 ppm by mass. (7) The residual molar ratio of phosphorus element to aluminum element in the polyester resin (B) is 1.00 or more and 5.00 or less.
[0120] The method for producing the polyester resin (B) preferably comprises: a first step of synthesizing a polyester or an oligomer thereof as a polycondensate (low-order condensate) as an intermediate, and a second step of further polycondensing the intermediate. When only chemically recycled BHET is used, or when the copolymerization component is a small amount, the first step may be omitted and the process may be started from the second step. However, when the copolymerization component is small, it is preferred that the copolymerization component is added to the chemically recycled BHET, or after the first step of synthesizing the oligomer using the copolymerization component and, if necessary, terephthalic acid or ethylene glycol, the oligomer obtained is mixed with the chemically recycled BHET and polymerized.
[0121] In addition, preferably, after the first step and before the second step, a solution S containing an aluminum compound and a solution T containing a phosphorus compound are added to the intermediate so as to satisfy the following (8) to (10). The polycarboxylic acid and its ester-forming derivatives, the hydroxycarboxylic acid and its ester-forming derivatives which may be added in a small amount, and the cyclic ester which may be added in a small amount used in the production of the polyester resin (B) are not distilled from the reaction system to the outside of the system during the polymerization, and almost 100% of the amount initially added to the system as a catalyst remains in the polyester resin (B) produced by the polymerization. Therefore, the mass of the "produced polyester resin" can be calculated from these input amounts. (8) The amount of aluminum element added to the produced polyester resin (B) is 5 to 50 ppm by mass (more preferably 7 to 40 ppm by mass, further preferably 10 to 30 ppm by mass, and particularly preferably 15 to 25 ppm by mass). (9) The amount of phosphorus added to the produced polyester resin (B) is 5 to 1500 ppm by mass (more preferably 10 to 500 ppm by mass, further preferably 20 to 200 ppm by mass, and particularly preferably 30 to 100 ppm by mass). (10) The molar ratio of the amount of phosphorus added in (9) to the amount of aluminum added in (7) (hereinafter referred to as "the molar ratio of phosphorus added to aluminum") is 1.00 or more and 7.00 or less (more preferably 1.50 to 6.00, and even more preferably 2.00 to 5.00).
[0122] There are no particular limitations on the method for producing the polyester or oligomer thereof which is the low-order polycondensate (oligomer) synthesized in the first step.
[0123] The method for producing the polyester resin (B) can be carried out by a method having conventionally known processes, except for using a polyester polymerization catalyst composed of an aluminum compound and a phosphorus compound as a catalyst and paying attention to the amount of the polyester polymerization catalyst added. For example, when producing polyethylene terephthalate, chemically recycled BHET and other copolymer components as required are directly reacted, and after distilling off water and esterification, polycondensation is carried out under normal pressure or reduced pressure to produce it. Furthermore, solid phase polymerization can be carried out as required to increase the intrinsic viscosity. In addition, the amount (mass) of the produced polyester resin (B) can be calculated from the amount (mass) of the polycarboxylic acid containing dicarboxylic acid and the like used as a raw material.
[0124] In any of these aspects, the esterification reaction or the transesterification reaction may be performed in one step or may be performed in a plurality of steps.
[0125] Furthermore, the polyester resin produced by the melt polymerization method may be subjected to additional polymerization by the solid phase polymerization method. The solid phase polymerization reaction can be carried out using a continuous apparatus similar to the melt polycondensation reaction.
[0126] In the case of a continuous polycondensation device consisting of three or more reactors (a three-stage polymerization method of an initial stage, an intermediate stage, and a late stage), the first stage is set as the initial stage, the final stage is set as the late stage, and the second stage to the stage before the final stage is set as the intermediate stage, and the reaction conditions of the polymerization reaction in the intermediate stage are preferably conditions between the reaction conditions of the initial stage and the reaction conditions of the final stage. It is preferred to smoothly distribute the degree of increase in the intrinsic viscosity reached by each of these polymerization reaction steps.
[0127] (Solid Phase Polymerization) In order to increase the intrinsic viscosity, the polyester resin produced by the melt polymerization method may be subjected to solid phase polymerization. The solid phase polymerization may be a batch polymerization method or a continuous polymerization method, but the solid phase polymerization is preferably carried out using a continuous apparatus like the melt polymerization.
[0128] In order to reduce the CT content of the polyester resin (B), it is preferred to perform additional polymerization on the polyester resin produced by the melt polymerization method by solid phase polymerization. The solid phase polymerization is carried out by making the polyester obtained by the second step (melt polymerization) into a powdery form. The powdery form refers to polyester in the form of chips, pellets, flakes, or powder, and chips or pellets are preferred.
[0129] The solid phase polymerization is carried out by heating the polyester in powder form at a temperature below the melting point of the polyester while flowing an inert gas or under reduced pressure. The solid phase polymerization step may be carried out in one stage or in multiple stages.
[0130] The powdery polyester to be supplied to the solid phase polymerization step may be supplied to the solid phase polymerization step after being preliminarily crystallized by heating to a temperature lower than the temperature at which solid phase polymerization is previously performed.
[0131] Such a pre-crystallization step can be carried out by heating the powdered polyester in a dry state at a temperature of usually 120 to 200°C, preferably 130 to 180°C, for 1 minute to 4 hours, or by heating the powdered polyester in a water vapor atmosphere, an inert gas atmosphere containing water vapor, or an air atmosphere containing water vapor, at a temperature of usually 120 to 200°C for more than 1 minute.
[0132] As described above, the melt-polymerized polyester is, for example, transported from a transport pipeline to a storage silo or a solid phase polymerization process after being fragmented. For example, when the transportation of such fragments is carried out by a forced air low-density transport method, the surface of the melt-polymerized polyester fragments is subjected to a large impact force due to the collision with the pipeline, resulting in a large amount of fine powder and film-like substances. Such fine powder and film-like substances have the effect of promoting the crystallization of polyester, and when they exist in large quantities, the transparency of the obtained molded body becomes very poor. Therefore, in one preferred embodiment, a process of removing such fine powder and film-like substances can be performed.
[0133] There is no limitation on the method for removing the above-mentioned fine powder and film-like material. For example, methods such as a vibration screening process and an air flow classification process of air flow, a gravity classification process, etc., which are separately provided in an intermediate process between the above-mentioned solid phase polymerization process and a subsequent process provided after the solid phase polymerization process, can be listed.
[0134] When an aluminum compound and a phosphorus compound are used as catalysts, they are preferably added in a slurry or solution form, more preferably a solution dissolved in a solvent such as water or glycol, further preferably a solution dissolved in water and / or glycol, and most preferably a solution dissolved in ethylene glycol.
[0135] Preferably, at any stage before the start of the polymerization reaction in the production process of the polyester resin (B), a solution S in which an aluminum compound is dissolved and a solution T in which a phosphorus compound is dissolved are added so that the content (residual amount) in the polyester resin (B) satisfies the ranges of (4) to (6) above.
[0136] By increasing the amount of solution S containing an aluminum compound and solution T containing a phosphorus compound added so that the content (residual amount) in the polyester resin (B) satisfies the above (4) to (6), a coordination compound having catalytic activity can be functionally formed in the polymerization system, thereby exerting sufficient polymerization activity. In addition, the generation of aluminum-based foreign matter can also be suppressed.
[0137] Furthermore, even if the aluminum element in the aluminum compound that functions as a catalyst is placed in a reduced pressure environment during the polymerization of the polyester resin, almost 100% of the amount initially added to the system as a catalyst remains in the polyester resin (B) produced by the polymerization. That is, the amount of the aluminum compound hardly changes before and after the polymerization, and therefore, when the amount of the aluminum element added is 5 to 50 mass ppm relative to the intermediate, the content of the aluminum element in the polyester resin (B) is also 5 to 50 mass ppm.
[0138] Furthermore, when the phosphorus compound that functions as a catalyst together with the aluminum compound is placed in a reduced pressure environment during the polymerization of the polyester resin, a portion (about 10 to 40%) of the amount initially added to the system as a catalyst is removed to the outside of the system, and the removal ratio varies depending on the added molar ratio of phosphorus element to aluminum element, the alkalinity or acidity of the solution containing the aluminum compound or the solution containing the phosphorus compound, the method of adding the aluminum-containing solution or the phosphorus-containing solution (homogeneous addition or separate addition), etc. Therefore, it is preferable to appropriately set the amount of the phosphorus compound added to the polyester resin (B) to be the final product so as to satisfy the above (5).
[0139] Preferably, the solution S in which the aluminum compound is dissolved and the solution T in which the phosphorus compound is dissolved are added simultaneously, the solution S in which the aluminum compound is dissolved and the solution T in which the phosphorus compound is dissolved are mixed in advance at the ratio added to the above intermediate to prepare a mixed solution, and then the mixed solution prepared as a single liquid is added to the above intermediate. As a method for preparing a single liquid in advance, a method of mixing the solutions in a container, a method of merging the pipelines for adding the catalyst on the way and mixing them, etc. can be cited. When adding to the reaction vessel, it is preferred to strengthen the stirring of the reaction vessel. When adding to the pipeline between the reaction vessels, it is preferred to install an in-line stirrer to quickly mix the added catalyst solution. When the solution S in which the aluminum compound is dissolved and the solution T in which the phosphorus compound is dissolved are added separately, a large amount of foreign matter caused by the aluminum compound is likely to be generated, the temperature of crystallization is lowered when the temperature is increased, and the temperature of crystallization is increased when the temperature is decreased, and sometimes the catalytic activity cannot be fully developed. By adding the aluminum compound and the phosphorus compound at the same time, a complex of the aluminum compound and the phosphorus compound that brings polymerization activity can be generated quickly and without waste, while when they are added separately, the complex of the aluminum compound and the phosphorus compound may not be generated sufficiently, and the aluminum compound that cannot generate a complex with the phosphorus compound may precipitate as foreign matter. In addition, the solution S in which the aluminum compound is dissolved and the solution T in which the phosphorus compound is dissolved are preferably added before the polymerization reaction starts and after the esterification reaction or the transesterification reaction is completed, and more preferably, the solution S in which the aluminum compound is dissolved and the solution T in which the phosphorus compound is dissolved are added to the intermediate after the first step and before the second step. When added before the esterification reaction or the transesterification reaction is completed, the amount of aluminum-based foreign matter may increase.
[0140] The solution S in which the aluminum compound is dissolved is preferably a diol solution in which the aluminum compound is dissolved, and the solution T in which the phosphorus compound is dissolved is preferably a diol solution in which the phosphorus compound is dissolved. The diol is preferably the diol used in the polyester resin (B), and more preferably ethylene glycol.
[0141] <Heat Treatment of Phosphorus Compounds> In addition, the phosphorus compound used in the production of the polyester resin (B) is preferably a phosphorus compound that has been heat-treated in a solvent. The solvent used is not limited as long as it is at least one selected from water and an alkylene glycol, but as the alkylene glycol, a solvent that dissolves the phosphorus compound is preferably used, and a diol that is a constituent component of the polyester resin (B) such as ethylene glycol is more preferably used. The heating treatment in the solvent is preferably performed after the phosphorus compound is dissolved, but it is not necessary to completely dissolve it.
[0142] The heat treatment conditions are preferably a heat treatment temperature of 170 to 196° C., more preferably 175 to 185° C., and even more preferably 175 to 180° C. The heat treatment time is preferably 30 to 240 minutes, and more preferably 50 to 210 minutes.
[0143] The concentration of the phosphorus compound during the heat treatment is preferably 3 to 10% by mass.
[0144] By the above-mentioned heat treatment, the acidity of the phosphorus compound contained in the diol solution can be kept constant, the polymerization activity brought about by the combined use of the aluminum compound can be improved, the generation of aluminum-based foreign matter caused by the polymerization catalyst can be reduced, and the distillation amount of the phosphorus compound in the polymerization step can be suppressed, thereby improving economic efficiency. Therefore, it is preferable to perform the above-mentioned heat treatment.
[0145] This application claims the benefit of priority based on Japanese Patent Application No. 2022-130152 filed on August 17, 2022. This application incorporates the entire contents of the specification of Japanese Patent Application No. 2022-130152 filed on August 17, 2022 for reference. [Example]
[0146] Hereinafter, the present invention will be described by way of examples, but the present invention is not limited to these examples. In addition, the evaluation methods used in each example and comparative example are as follows.
[0147] [Evaluation Method] (1) Intrinsic viscosity (IV) About 3 g of the sample was freeze-ground and dried at 140°C for 15 minutes, then 0.20 g was weighed and stirred at 100°C for 60 minutes using 20 ml of a mixed solvent of 1,1,2,2-tetrachloroethane and p-chlorophenol at a mass ratio of 1:3. After complete dissolution and cooling to room temperature, the sample was filtered through a glass filter. The falling time of the sample and the solvent was measured using an Ubbelohde viscometer (manufactured by Rigo Co., Ltd.) adjusted to 30°C, and the intrinsic viscosity [η] was calculated using the following formula. [η]=(-1+√(1+4K'ηSp)) / 2K'C ηSp=(τ-τ0)τ0 Here, [η]: Intrinsic viscosity (dl / g) ηSp: Specific viscosity (-) K': Huggins constant (= 0.33) C: concentration (=1g / dl) τ: Sample drop time (sec) τ0: solvent falling time (sec)
[0148] (2) Content of the specified metal element in the sample The following polyester resin (A1) was weighed in a platinum crucible, carbonized in an electric furnace, and then ashed in a muffle furnace at 550°C for 8 hours. The ashed sample was dissolved in 1.2M hydrochloric acid to obtain a sample solution. The prepared sample solution was measured under the following conditions, and the concentrations of antimony, germanium and titanium in the polyester resin (A1) were determined by high-frequency inductively coupled plasma emission spectrometry. The concentration of antimony in the following polyester resin (D1) was determined in the same manner. In addition, the concentration of aluminum in the following polyester resins (B1), (B2) and (B3) was determined in the same manner as above. Device: CIROS-120 manufactured by SPECTRO Plasma power: 1400W Plasma gas: 13.0L / min Auxiliary gas: 2.0L / min Atomizer: Cross-flow nebulizer Atomization chamber: Cyclone chamber Measurement wavelength: 167.078nm
[0149] (3) Phosphorus content in polyester resin (B) 0.2 g of polyester resin (B1) was wet decomposed with 3 mL of 97% by mass sulfuric acid, 3 mL of 60% by mass nitric acid, and 0.5 mL of 60% by mass perchloric acid, and then neutralized with aqueous ammonia. After adding 0.3 mL of 2% by mass ammonium molybdate and 0.3 mL of 0.5% by mass hydrazine sulfate to the prepared solution, the absorbance at a wavelength of 830 nm was measured using an ultraviolet visible spectrophotometer (manufactured by Shimadzu Corporation, UV-1700). The concentration of phosphorus in polyester resin (B1) was determined from a pre-made standard curve. Similarly, the concentration of phosphorus in polyester resins (B2), (B3), and (B4) was determined. In addition, the sample amount of the polyester resin can be adjusted according to the concentration of phosphorus in the polyester resin.
[0150] (4) Amount of aluminum foreign matter in polyester resin (B) 30g of polyester resin (B1) and 250mL of a mixed solution of p-chlorophenol / tetrachloroethane (3 / 1: mass ratio) were placed in a 500mL conical flask with a stirrer, and heated and dissolved at 100-105°C for 1.5 hours using a heating stirrer. The solution was filtered using a polytetrafluoroethylene membrane filter with a diameter of 47mm / pore size of 1.0μm (PTFE membrane filter manufactured by Advantec, product name: T100A047A) to filter out foreign matter. The effective filter diameter is 37.5mm. After the filtration is completed, it is then washed with 50mL of chloroform and the membrane is dried. The amount of aluminum on the filter surface of the membrane filter was quantified using a scanning fluorescent X-ray analyzer (Rigaku Co., Ltd., ZSX100e, Rh light tube 4.0kW). The quantification was performed on the portion with a diameter of 30 mm at the center of the membrane filter. In addition, the standard curve of the fluorescent X-ray analysis method was obtained using polyethylene terephthalate resin with a known aluminum content, and the apparent aluminum content was expressed in ppm. In the measurement, pentaerythritol was used as a spectroscopic crystal with an X-ray output of 50kV-70mA, a PC (proportional counter) was used as a detector, and the Al-Kα ray intensity was measured under the conditions of PHA (wave height analyzer) 100-300. The standard curve was quantified using the aluminum content in the polyethylene terephthalate resin by high-frequency inductively coupled plasma emission analysis. The amount of aluminum-based foreign matter in the polyester resins (B2), (B3), and (B4) was similarly obtained.
[0151] (5) Confirmation of the presence of hindered phenol structures or their decomposed residues in the sample 420 mg of the sample was dissolved in 2.7 mL of a mixed solvent of hexafluoroisopropanol and deuterated benzene at a ratio of 1:1 (mass ratio), and 10 μL of a 25% deuterated acetone solution of phosphoric acid was added and centrifuged. Then, 100 to 150 mg of trifluoroacetic acid was added to the supernatant and P-NMR measurement was immediately performed under the following conditions. Apparatus: Fourier transform nuclear magnetic resonance apparatus (made by BRUKER, AVANCE500) 31P resonance frequency: 202.456MHz Locking solvent: deuterated benzene Flip angle of detection pulse: 65° Data acquisition time: 1.5 seconds Delay time: 0.5 seconds Proton decoupling: Complete decoupling Measuring temperature: 25~35℃ Cumulative times: 20,000 to 30,000 times The peak wavelengths of the residues of the chemical formula numbers shown in Table 1 are shown below. When these peak wavelengths are detected, it is determined that the sample has a hindered phenol structure. Chemical formula 1: 34.5ppm, Chemical formula 4: 30.5ppm, Chemical formula 7: 53.6ppm Chemical formula 2: 33.8ppm, Chemical formula 5: 30.1ppm, Chemical formula 8: 53.0ppm Chemical formula 3: 31.9ppm, Chemical formula 6: 28.7ppm, Chemical formula 9: 51.3ppm
[0152] (6) Quantitative measurement of the annular tripartite Freeze-crush or slice the sample, and accurately weigh 100 mg of the sample. Dissolve it in 3 mL of a hexafluoroisopropanol / chloroform mixture (volume ratio = 2 / 3), and further add 20 mL of chloroform to dilute it. Add 10 mL of methanol to precipitate the polymer, and then filter. Evaporate the filtrate to dryness and make the volume up to 10 mL with dimethylformamide. Then, use the following high performance liquid chromatography to quantify the amount of cyclic ternary bodies in the polyester resin. Repeat the above operation 5 times, and take the average value as the CT content. Device: L-7000 (manufactured by Hitachi, Ltd.) Column: μ-Bondasphere C18 5μ 3.9mm×15cm (made by Waters) Solvent: Eluent A: 2% acetic acid / water (v / v) Eluent B: acetonitrile Gradient B%: 10→100% (0→55 min) Flow rate: 0.8 mL / min Temperature: 30℃ Detector: UV-259nm
[0153] (7) Intrinsic viscosity retention rate of the sample The sample was dried at 140°C for 16 hours by vacuum drying until the moisture content was below 150ppm. When the sample was a film, the film was cut into pieces of about 1cm square. For resin pellets, the pellets were used directly as samples. Using the dried polyester, the re-refined product was subjected to one re-refining treatment using a twin-screw extruder under the following conditions, and the intrinsic viscosity of the re-refined product was measured. The intrinsic viscosity retention rate was calculated using the following formula. In addition, using the above-mentioned dried polyester resin, the re-refined product was subjected to three re-refining treatments using a twin-screw extruder under the following conditions, and the intrinsic viscosity of the re-refined product was measured. The intrinsic viscosity retention rate was calculated using the following formula. In addition, the method for measuring the intrinsic viscosity is as described in (1) above. Twin-screw extruder: KZW15TW-45 / 60MG-NH (-2200) manufactured by Technovel Set temperature: 260℃ (actual temperature 268~270℃) Screw speed: 200rpm Discharge: 1.7~2.0kg / h Intrinsic viscosity retention rate (%) = 100 × intrinsic viscosity of re-refined product / intrinsic viscosity of sample The water content of 0.6 g of a sample was measured using a coulometric Karl Fischer titrator (CA-200 manufactured by Mitsubishi Chemical Analytech Co., Ltd.) at 230° C. for 5 minutes in a nitrogen gas flow of 250 mL / min.
[0154] (8) Composition Analysis of Polyester Resin (A1) 20 mg of the polyester resin (A1) was dissolved in 0.6 ml of a mixed solvent of deuterated hexafluoroisopropanol and deuterated chloroform at a ratio of 1:9 (volume ratio), and the mixture was centrifuged. Then, the supernatant was collected and subjected to H-NMR measurement under the following conditions. Apparatus: Fourier transform nuclear magnetic resonance apparatus (made by BRUKER, AVANCE NEO600) 1H resonance frequency: 600.13MHz Lock solvent: deuterated chloroform Flip angle: 30° Data collection time: 4 seconds Delay time: 1 second Measurement temperature: 30℃ Cumulative times: 128 times
[0155] (9) Contents of dicarboxylic acid components and diol components in BHET Chemically recycled BHET was dissolved in deuterated methanol and subjected to H-NMR measurement under the following conditions. Apparatus: Fourier transform nuclear magnetic resonance apparatus (manufactured by BRUKER) 1H resonance frequency: 500.13MHz Lock solvent: deuterated methanol Flip angle: 45° Data collection time: 4 seconds Delay time: 1 second Measurement temperature: 27℃ Cumulative times: 36 times
[0156] The preparation of the ethylene glycol solution containing aluminum and the ethylene glycol solution containing phosphorus will be described below.
[0157] <Preparation of Aluminum-Containing Ethylene Glycol Solution S> An equal amount (volume ratio) of ethylene glycol to a 20 g / L aqueous solution of basic aluminum acetate is added to a mixing tank, and after stirring at room temperature (23°C) for several hours, water is distilled off from the system while stirring at reduced pressure (3 kPa) and 50 to 90°C for several hours to prepare an aluminum-containing ethylene glycol solution S containing 20 g / L of aluminum compound.
[0158] <Preparation of Phosphorus-Containing Ethylene Glycol Solution T> Irganox 1222 (manufactured by BASF) as a phosphorus compound and ethylene glycol were simultaneously added to a mixing tank, and after nitrogen substitution, heat treatment was performed at 175° C. for 150 minutes while stirring to prepare a phosphorus-containing ethylene glycol solution T containing 50 g / L of the phosphorus compound.
[0159] 〔Manufacture of polyester resin〕 Polyester resin (B1) Chemically recycled BHET was added to a 10L stainless steel autoclave equipped with a stirrer, and a mixed solution prepared by mixing the aluminum-containing ethylene glycol solution S and the phosphorus-containing ethylene glycol solution T prepared by the above method to form a single liquid was added. The mixed solution was prepared so that the aluminum element and the phosphorus element were 21 mass ppm and 58 mass ppm, respectively, based on the mass of the obtained polyester. The added molar ratio of the phosphorus element to the aluminum element was 2.41. Then, the temperature of the system was raised to 280°C over 1 hour, during which the pressure of the system was slowly reduced to 0.15 kPa, and a polycondensation reaction was carried out under this condition to obtain a polyester resin having an intrinsic viscosity IV of 0.60 dl / g. Then, the obtained polyester resin was extruded into a strip shape and cut into a pellet shape of 2.5×3×4 mm, and then solid-phase polymerized at 230°C under reduced pressure for 7 hours using a batch-type solid-phase polymerization device to obtain a polyester resin (B1) having an intrinsic viscosity IV of 0.75 dl / g and a CT content of 4600 mass ppm. The residual amount of aluminum element in the polyester resin (B1) was 21 mass ppm, the residual amount of phosphorus element was 45 mass ppm, and the residual molar ratio of phosphorus element to aluminum element was 1.87. The content of aluminum element equivalent to aluminum-based foreign matter in the polyester resin (B1) was 710 mass ppm, and the L value of the polyester resin (B-1) was 58.5, and it was confirmed that the polyester resin (B1) had a hindered phenol structure. The intrinsic viscosity retention rate of the first remilling was 98%, and the intrinsic viscosity retention rate of the third remilling was 88%. In addition, the chemically recycled BHET used was obtained by alkaline hydrolysis of recycled PET bottles and polyester fibers in ethylene glycol, followed by purification processes such as filtration and distillation. The isophthalic acid component in the chemically recycled BHET was 1.0 mol% (relative to the total acid components), and the diethylene glycol component was 1.2 mol% (relative to the total acid components).
[0160] Polyester resin (B2) A polyester resin (B2) having an intrinsic viscosity of 0.75 dl / g and a CT content of 4600 mass ppm was obtained by the same method as the polyester resin (B1), except that the addition amounts of the aluminum element and the phosphorus element were different. The residual amount of the aluminum element in the polyester resin (B2) was 16 mass ppm, the residual amount of the phosphorus element was 26 mass ppm, and the residual molar ratio of the phosphorus element to the aluminum element was 1.42. The content of the aluminum element, which was equivalent to aluminum-based foreign matter in the polyester resin (B2), was 2000 mass ppm, and the L value of the polyester resin (B2) was 58.5, confirming that the polyester resin (B2) had a hindered phenol structure. The intrinsic viscosity retention rate of the first re-milling was 97%, and the intrinsic viscosity retention rate of the third re-milling was 87%.
[0161] Polyester resin (B3) A polyester resin (B3) having an intrinsic viscosity of 0.75 dl / g and a CT content of 4600 mass ppm was obtained by the same method as the polyester resin (B1), except that the addition amounts of the aluminum element and the phosphorus element were different. The residual amount of the aluminum element in the polyester resin (B3) was 10 mass ppm, the residual amount of the phosphorus element was 16 mass ppm, and the residual molar ratio of the phosphorus element to the aluminum element was 1.39. The content of the aluminum element, which is equivalent to aluminum-based foreign matter in the polyester resin (B3), was 2300 mass ppm, and the L value of the polyester resin (B3) was 56.7, confirming that the polyester resin (B3) had a hindered phenol structure. The intrinsic viscosity retention rate of the first re-milling was 96%, and the intrinsic viscosity retention rate of the third re-milling was 86%.
[0162] Polyester resin (B4) The polyester resin (B1) and silica particles having an average particle size of 2.5 μm were charged into a twin-screw extruder and kneaded at 285° C. to prepare pellets of a masterbatch having a silica particle content of 10,000 ppm.
[0163] Polyester resin (D1) Pellets of polyethylene terephthalate (antimony element content: 230 mass ppm, intrinsic viscosity: 0.75 dl / g) using antimony trioxide as a catalyst were prepared.
[0164] Polyester resin (D2) The polyester resin (D1) and silica particles having an average particle size of 2.5 μm were charged into a twin-screw extruder and kneaded at 285° C. to prepare pellets of a masterbatch having a silica particle content of 6000 ppm.
[0165] 〔Recycled polyester resin〕 Polyester resin (A1) As polyester resin (A1), a recycled polyester resin flake provided by Kyoei Industry Co., Ltd. was used. The result of the composition analysis of the recycled polyester resin flake was a composition containing 1.7 mol% of isophthalic acid component and 2.1 mol% of diethylene glycol component, and the CT content was 4900 ppm. The size of the flake was 8.6 mm. The intrinsic viscosity of the recycled polyester resin flake was 0.750 dl / g. In addition, the content of antimony element in the above-mentioned recycled polyester resin flake was 190 mass ppm, and the content of germanium element was 1.6 mass ppm. In addition, the content of titanium element was less than 1 mass ppm, which was very small, so the content of titanium element was omitted in Tables 2 and 3. It can be explained from the content of each element of antimony, germanium, and titanium that the above-mentioned recycled polyester resin flake is a recycled polyester resin flake mainly composed of a hollow molded body of a polyester resin produced by an antimony catalyst. The intrinsic viscosity retention rate of the first re-refining of the polyester resin (A1) was 88%, and the intrinsic viscosity retention rate of the third re-refining was 77%.
[0166] (Examples, Comparative Examples, Reference Examples) Each polyester resin was supplied to a single screw extruder at the formulation ratio (parts by mass) shown in Table 2 and melted at 290°C. The molten polymer was filtered using a filter material (nominal filtration accuracy: interception of 95% of 20 μm particles) of a stainless steel sintered body, extruded from a die into a sheet on a casting drum with a surface temperature of 30°C, and then cooled and solidified to produce an unstretched film. In addition, in order to prevent segregation during the supply of the polyester resin, a small amount was mixed and fed into the hopper each time. The unstretched film was stretched 3.3 times in the longitudinal direction at 95°C using rolls having a peripheral speed difference.
[0167] Next, the uniaxially stretched film was introduced into a tenter stretching machine, and while holding the ends of the film with a clamp, it was introduced into a hot air zone at a temperature of 125°C and stretched to 3.5 times in the width direction. Then, the stretched width in the width direction was maintained, and a heat setting treatment was performed at a temperature of 220°C for 10 seconds, and a relaxation treatment of 3.0% was further performed. Then, the two ends (ear-shaped parts) of the film cooled to 120°C were cut with a shear cutter to obtain a biaxially stretched PET film with a film thickness of 75 μm. The film was wound on a paper roll.
[0168] Evaluation of membrane recovery and reusability The films produced in Examples and Comparative Examples and the recovered ear-shaped portions were cut, and the cut film pieces were fed into a twin-screw extruder and melt-kneaded at 290° C. to prepare pellets, and the obtained pellets were melt-kneaded again at 290° C. to prepare pellets. A film was prepared in the same manner using the obtained secondary pellets, and the film was wound around a paper tube to prepare a remelted resin film. The side of the wound film was observed to see the difference in color tone. ○: No difference in color tone was felt. △: The re-melted resin film side is slightly yellowish. ×: The re-melted resin film side has a distinct yellow tint.
[0169]
Table 2
[0170] Embodiments 12 to 15 The polyester resin for the intermediate layer shown in Table 3 was supplied to extruder 1, and the polyester resin for the surface layer was supplied to extruder 2 and dissolved at 285° C. Two types of three-layer metal dies were used to produce a biaxially stretched PET film except that the thickness of the surface layer / intermediate layer / surface layer was 1 / 8 / 1. In addition, in the evaluation of recovery and recyclability of the film, the same single-layer structure as in Example 1 was formed.
[0171]
Table 3
[0172] Embodiments 16 to 17 As polyester resin (A2), a recycled sheet of ear-shaped parts obtained from another polyester film production line (IV = 0.61 dl / g, Sb content: 140 ppm, lubricant particles are trace amounts) was prepared, and as polyester resin (B5), a resin having an intrinsic viscosity of 0.67 dl / g was prepared by melt polymerization alone in the same manner as polyester resin (B1), and a film was prepared in the same manner as in Example 1 using the polyester resins in Table 4. In addition, after being stretched in the longitudinal direction, an easy-adhesive coating material of the following composition was applied to both sides of the film and then introduced into a tenter to form a biaxially stretched PET having easy-adhesive layers on both sides.
[0173] (Preparation of Easy-Adhesion Coating) By carrying out transesterification and polycondensation by a conventional method, a water-dispersible copolyester resin containing a sulfonic acid metal base was prepared, which had a composition of 46 mol% of terephthalic acid, 46 mol% of isophthalic acid and 8 mol% of sodium 5-sulfoisophthalate as dicarboxylic acid components (relative to the total dicarboxylic acid components), and 50 mol% of ethylene glycol and 50 mol% of neopentyl glycol as diol components (relative to the total diol components). Then, 51.4 parts by mass of water, 38 parts by mass of isopropyl alcohol, 5 parts by mass of n-butyl cellosolve and 0.06 parts by mass of a nonionic surfactant were mixed, and heated and stirred. When the mixture reached 77° C., 5 parts by mass of the water-dispersible copolyester resin containing a sulfonic acid metal base was added. After continued stirring until the resin lumps disappeared, the resin aqueous dispersion was cooled to room temperature to obtain a uniform water-dispersible copolyester resin liquid having a solid content concentration of 5.0% by mass. Furthermore, 3 parts by mass of agglomerated silica particles (SYLYSIA310 manufactured by Fuji Silysia Co., Ltd.) were dispersed in 50 parts by mass of water, and then 0.54 parts by mass of an aqueous dispersion of SYLYSIA310 was added to 99.46 parts by mass of the above-mentioned water-dispersible copolyester resin liquid, and 20 parts by mass of water were added while stirring to obtain an easy-adhesive coating.
[0174]
Table 4
[0175] As shown in Table 2, although the intrinsic viscosity retention rate tends to decrease as the amount of polyester resin (B1) decreases in Examples 1 to 6, the intrinsic viscosity retention rate is still higher than that of Comparative Example 1, Comparative Example 2, and Reference Example. As in Examples 7 to 11, the intrinsic viscosity retention rate is also higher for polyester resins (B2) and (B3) with low aluminum content and phosphorus content to reduce costs. In the examples, there is no problem of coloring of the end surface of the coil after re-filming.
[0176] Examples 12 to 15 in Table 3 are examples in which the recycled polyester resin A1 is used in the intermediate layer. In the examples, there is no problem of coloration of the end surface of the web after re-filming. Examples 16 and 17 in Table 4 are examples using recycled polyester resin from the film production process. In these examples, there was no problem of coloration of the end surface of the web after re-filming. [Possible industrial applications]
[0177] By mixing a polyester resin (B) obtained from bis-2-hydroxyethyl terephthalate obtained by chemical recycling and containing an aluminum compound and a phosphorus compound as a raw material with a recycled polyester resin (A), the polyester film can be produced, and coloration and molecular weight reduction of the polyester film can be suppressed, and a polyester film with excellent recycling efficiency can be obtained. According to the present invention, it is possible to contribute to solving various problems such as suppressing resource depletion, reducing marine garbage, and suppressing global warming.
Claims
1. A method for producing a polyester film, characterized in that: include: A step of mixing the recovered polyester resin A with a polyester resin B containing an aluminum compound and a phosphorus compound, wherein the polyester resin A satisfies the following (1) to (3), and the polyester resin B satisfies the following (4), (1) the polyester resin A contains at least one element selected from antimony, titanium and germanium, (2) the total content of antimony, titanium and germanium in the polyester resin A is 2 to 500 ppm by mass, (3) The intrinsic viscosity of the polyester resin A is 0.5 to 0.8 dl / g, (4) The polyester resin B is a resin obtained by polycondensing a raw material containing di-2-hydroxyethyl terephthalate obtained by decomposing a polyester resin.
2. The method for producing a polyester film according to claim 1, wherein The polyester resin B satisfies the following (5) and (6), (5) The content of aluminum in the polyester resin B is 5 to 50 ppm by mass, (6) The phosphorus content in the polyester resin B is 5 to 1000 ppm by mass.
3. The method for producing a polyester film according to claim 1, wherein The mixing step includes: melt-mixing the polyester resin A and the polyester resin B to prepare a polyester resin composition C.
4. The method for producing a polyester film according to claim 1, wherein The mixing step includes further mixing a polyester resin D different from the polyester resin A and the polyester resin B.
5. A method for producing a polyester film, characterized in that: include: A step of mixing a polyester resin composition C which is a molten mixture of a recovered polyester resin A and a polyester resin B containing an aluminum compound and a phosphorus compound with a polyester resin D which is different from the polyester resin A and the polyester resin B, wherein the polyester resin A satisfies the following (1) to (3) and the polyester resin B satisfies the following (4), (1) the polyester resin A contains at least one element selected from antimony, titanium and germanium, (2) the total content of antimony, titanium and germanium in the polyester resin A is 2 to 500 ppm by mass, (3) The intrinsic viscosity of the polyester resin A is 0.5 to 0.8 dl / g, (4) The polyester resin B is a resin obtained by polycondensing a raw material containing di-2-hydroxyethyl terephthalate obtained by decomposing a polyester resin.
6. The method for producing a polyester film according to claim 3 or 5, wherein: The intrinsic viscosity retention rate of the polyester resin composition C obtained by the following formula is 89% or more, Intrinsic viscosity retention rate, % = intrinsic viscosity of the sample after 1 re-refining / intrinsic viscosity of the sample × 100 The first remilling sample is a sample that has passed through a twin-screw extruder under the conditions of a temperature of 260° C., a screw speed of 200 rpm, and an output of 1.7 to 2.0 kg / h. The intrinsic viscosity is calculated by supplying a solution of 0.2 g of the sample and 20 ml of a mixed solvent of 1,1,2,2-tetrachloroethane and p-chlorophenol to an Ubbelohde viscometer at 30° C., wherein the mass ratio of 1,1,2,2-tetrachloroethane to p-chlorophenol in the mixed solvent is 1:
3.
7. The method for producing a polyester film according to claim 1 or 5, wherein: The intrinsic viscosity retention rate of the polyester resin A obtained by the following formula is 92% or less, Intrinsic viscosity retention rate, % = intrinsic viscosity of the sample after 1 re-refining / intrinsic viscosity of the sample × 100 The first re-milled sample is a sample that has passed through a twin-screw extruder under the conditions of a temperature of 260°C, a screw speed of 200 rpm, and an output of 1.7 to 2.0 kg / h. The intrinsic viscosity is calculated by supplying a solution of 0.2 g of the sample and 20 ml of a mixed solvent of 1,1,2,2-tetrachloroethane and p-chlorophenol to an Ubbelohde viscometer at 30°C, wherein the mass ratio of 1,1,2,2-tetrachloroethane to p-chlorophenol in the mixed solvent is 1:
3.
8. The method for producing a polyester film according to claim 1 or 5, wherein: The intrinsic viscosity retention rate of the polyester resin B obtained by the following formula is 93% or more, Intrinsic viscosity retention rate, % = intrinsic viscosity of the sample after 1 re-refining / intrinsic viscosity of the sample × 100 The first remilling sample is a sample that has passed through a twin-screw extruder under the conditions of a temperature of 260° C., a screw speed of 200 rpm, and an output of 1.7 to 2.0 kg / h. The intrinsic viscosity is calculated by supplying a solution of 0.2 g of the sample and 20 ml of a mixed solvent of 1,1,2,2-tetrachloroethane and p-chlorophenol to an Ubbelohde viscometer at 30° C., wherein the mass ratio of 1,1,2,2-tetrachloroethane to p-chlorophenol in the mixed solvent is 1:
3.
9. The method for producing a polyester film according to claim 4 or 5, wherein: The polyester resin composition E containing the polyester resin A, the polyester resin B and the polyester resin D has an intrinsic viscosity retention rate of 89% or more obtained by the following formula: Intrinsic viscosity retention rate, % = intrinsic viscosity of the sample after 1 re-refining / intrinsic viscosity of the sample × 100 The first remilling sample is a sample that has passed through a twin-screw extruder under the conditions of a temperature of 260° C., a screw speed of 200 rpm, and an output of 1.7 to 2.0 kg / h. The intrinsic viscosity is calculated by supplying a solution of 0.2 g of the sample and 20 ml of a mixed solvent of 1,1,2,2-tetrachloroethane and p-chlorophenol to an Ubbelohde viscometer at 30° C., wherein the mass ratio of 1,1,2,2-tetrachloroethane to p-chlorophenol in the mixed solvent is 1:
3.
10. The method for producing a polyester film according to claim 1 or 5, wherein: The content of the polyester resin A is 5 to 95 parts by mass based on 100 parts by mass of the total of the polyester resin A and the polyester resin B.
11. The method for producing a polyester film according to claim 4 or 5, wherein: The content of the polyester resin D is 5 to 95 parts by mass based on 100 parts by mass of the total of the polyester resin A, the polyester resin B, and the polyester resin D.
12. The method for producing a polyester film according to claim 1 or 5, wherein: The polyester film is a multilayer polyester film composed of at least two layers, and at least one surface layer is a layer containing no polyester resin A.
13. The method for producing a polyester film according to claim 1 or 5, wherein: The phosphorus compound has a phosphorus element and a phenol structure in the same molecule.
14. The method for producing a polyester film according to claim 1 or 5, wherein: The polyester resin A contains at least antimony element and germanium element.
15. The method for producing a polyester film according to claim 1 or 5, wherein: The polyester resin A contains at least an isophthalic acid structural unit as a copolymerization component.
16. A polyester film, characterized in that The polyester film is composed of a polyester resin composition E, wherein the polyester resin composition E contains: a recycled polyester resin A and a polyester resin B containing an aluminum compound and a phosphorus compound, wherein the polyester resin A satisfies the following (1) to (3), and the polyester resin B satisfies the following (4). (1) the polyester resin A contains at least one element selected from antimony, titanium and germanium, (2) the total content of antimony, titanium and germanium in the polyester resin A is 2 to 500 ppm by mass, (3) The intrinsic viscosity of the polyester resin A is 0.5 to 0.8 dl / g, (4) The polyester resin B is a resin obtained by polycondensing a raw material of di-2-hydroxyethyl terephthalate containing a polyester resin decomposition component.
17. The polyester film according to claim 16, wherein The polyester resin B satisfies the following (5) and (6), (5) The content of aluminum in the polyester resin B is 5 to 50 ppm by mass, (6) The phosphorus content in the polyester resin B is 5 to 1000 ppm by mass.
18. The polyester film according to claim 16 or 17, wherein The polyester resin composition E further contains a polyester resin D different from the polyester resin A and the polyester resin B.
19. The polyester film according to claim 16 or 17, wherein The intrinsic viscosity retention rate of the polyester resin composition E obtained by the following formula is 89% or more, Intrinsic viscosity retention rate, % = intrinsic viscosity of the sample after 1 re-refining / intrinsic viscosity of the sample × 100 The first remilling sample is a sample that has passed through a twin-screw extruder under the conditions of a temperature of 260° C., a screw speed of 200 rpm, and an output of 1.7 to 2.0 kg / h. The intrinsic viscosity is calculated by supplying a solution of 0.2 g of the sample and 20 ml of a mixed solvent of 1,1,2,2-tetrachloroethane and p-chlorophenol to an Ubbelohde viscometer at 30° C., wherein the mass ratio of 1,1,2,2-tetrachloroethane to p-chlorophenol in the mixed solvent is 1:
3.
20. The polyester film according to claim 16 or 17, wherein The polyester resin composition E constituting the film contains at least antimony element, germanium element, phosphorus element and aluminum element.
21. The polyester film according to claim 20, wherein At least one polyester resin contained in the polyester resin composition E constituting the film contains an isophthalic acid structural unit as a copolymerization component.
22. The polyester film according to claim 16 or 17, wherein The content ratio of antimony element / aluminum element is 0.5 or more and 200 or less on a mass basis.
23. The polyester film according to claim 16 or 17, wherein The content ratio of antimony element / (aluminum element and phosphorus element) is 0.1 or more and 100 or less on a mass basis.
Citation Information
Patent Citations
Polyester and method for producing polyester
JP2006169432A
Object recognition system and object recognition method
JP2022130152A
Polyester, process for production of polyester, and polyester molded article
WO2007032325A1
Polyester blow-molded article, and method for modling polyester blow-molded article
WO2013154042A1
Polyester blow-molded article, and method for modling polyester blow-molded article
WO2013154043A1
Cited By
Recycled content polyester compositions and methods of making and using the same
WO2026198324A1